Seasonal dynamics of geogenic phosphorus in alluvial-lacustrine aquifers: Coupling of phosphorus-containing dissolved organic matter and microbes as a key driver - Junna Ning; Yao Du; Baisong Deng; Mengze Li; Tianming Wu; Lijie Lin; Taiping Yu; Yiqun Gan; Dandan Si; Wen Zhang; Yanxin Wang (Water Research, 2027)

Aromatic carbon from low-temperature biochar enhances bacterial phosphorus solubilization under saline-alkaline stress - Ziyi Ge; Shiyun Gan; Jiayi Li; Ziyue Xu; Siyu Wang; Xu Su; Yixuan Chen; Li Lin; Song Gao; Jun Meng (Bioresource Technology, 2027)

Interfacial dual regulation of charge density and structural accessibility for efficient electrodialytic lithium extraction - Shuaibo Zhu; Ning Gan; Shuzhen Zhao; Erda Deng; Pengfei Zhang; Mengyang Hu; Xiao Xu; Xiaowei Zhu; Kecheng Guan; Tomohisa Yoshioka; Yuqing Lin; Hideto Matsuyama; et al. (Water Research, 2026)

FUT2-mediated α1,2-fucosylation in inflammatory bowel disease: mechanisms and translational potential - Jin Chen; Li Gan; Shuhong Zhang; Shengtao Liao; Lin Lv (Molecular Biology Reports, 2026)

Astaxanthin activates PI3K/AKT and AMPK signaling to alleviate oxidative stress and improve mouse oocyte In vitro maturation - Mei Zhou; Mengzhen Luo; Yueming Yuan; Liqin Han; Lin Chen; Shangquan Gan (Theriogenology, 2026)

Amorphous fluoropolymer OSRO membranes for highly-efficient hydrocarbon fractionation - Joy Thomas; Ning Gan; Hiroki Hayashi; Wakako Hashimoto; Natsuko Mikami; Tooru Kitagawa; Kuo-Lun Tung; Yuqing Lin; Hideto Matsuyama (Chemical Engineering Journal, 2026)

Spatial distribution, thickness characteristics, and environmental controls on soil organic carbon stocks of the mattic layer across the Qinghai-Tibetan Plateau - Jun Gu; Ming-Liang Ye; Fei Yang; Xiao-Dong Song; Alla Yurova; Gan-Lin Zhang (CATENA, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

Low-temperature direct regeneration of spent LiFePO4 cathodes via thiourea-assisted targeted PVDF degradation - Lei Gan; Weihao Lin; Weiliang Peng; Renzong Hu; Yuyin Li; Bin Yuan (Chemical Engineering Journal, 2026)

Probe-based near-infrared autofluorescence detection versus carbon nanoparticles for intraoperative parathyroid gland identification in thyroid surgery: A prospective study - Liangyu Gan; Qing Lin; Houjie Liu; Zheng Fang; Wanxue Zhang; Guangjin Yu; Biao Sun; Bin Liu; Yusheng Ye (Chemical Engineering Journal, 2026)

Bamboo expansion into broadleaf forests restructures topsoil carbon, nitrogen, phosphorus and potassium pools: A trade-off between carbon sink enhancement and nutrient limitation - Qiudi Wu; Xin Wang; Bing Ma; Hongwei Zhou; Chenyang Huang; Liangjie Wang; Youjin Yan; Ziqiang Liu; Lina Mei; Haibo Hu; Lin Chen; Fengling Gan; et al. (CATENA, 2026)

ROBO1 is required for postnatal growth and survival - Nicole Aurora Kirk; Ye Eun Hwang; Seul Gi Lee; Juyeon Kang; Kate-Lin Ly; Yong Yu Gan; Sangmyung Rhee; Kee-Beom Kim; Kwon-Sik Park (Genes & Genomics, 2026)
Roundabout guidance receptor 1 (ROBO1) is critical for various processes essential to mammalian development. However, its role in postnatal development and growth remains poorly understood, primarily due to perinatal lethality in knockout models. Robo1 knockout mice on a mixed B6/129S genetic background survive into adulthood and exhibit previously unreported abnormalities across multiple organs. These mice display stunted growth and organ-specific defects, including enlarged lung alveoli, premature hair graying, and diminished subcutaneous fat. Notably, these mice have a reduced lifespan. At 23 days of age, corresponding to the beginning of early puberty in mice, Robo1 knockout mice show significantly reduced plasma levels of growth hormone (GH) and insulin-like growth factor 1 (IGF-1), paralleling decreased expression in the pituitary gland and liver, respectively, compared to wild-type littermates. These findings suggest that ROBO1 contributes to the postnatal development and functional maintenance of multiple organs, with associated modulation of the GH/IGF-1 axis, potentially influencing survival. Further studies with larger cohorts are warranted to elucidate the broader implications of ROBO1 deficiency, particularly in relation to human developmental disorders such as growth hormone deficiencies.

Chilling tolerance in kiwifruit alleviated by brassinosteroid: roles in ROS scavenging, membrane lipid stabilization, and energy metabolism - Yupei Zhang; Lin Shen; Zhenyu Huang; Congcong Yang; Caining Yang; Kangyuan Xie; Huaxuan Hu; Chuying Chen; Yingying Yang; Ming Chen; Wenbin Kai; Jiaoke Zeng; et al. (Food Chemistry, 2026)

Eccentric compressive performance of CFST columns reinforced with annular stiffeners - Ke-Rong Luo; Bing-Lin Lai; Liang Yu; Bu-Hui Li; Gan-Ping Shu (Engineering Structures, 2026)

An effective strategy for rare microdissection testicular sperm involves utilizing a micro-cryopreservation technique combined with laser-assisted selection of immotile sperm after thawing - Ruoyun Lin; Caizhu Wang; Kongrong Xu; Jinhui Shu; Hanji Huang; Zhijian Chen; Xianyou Gan; Huanhua Chen (Cryobiology, 2026)

Scenario-based mapping reveals soil organic carbon responses to land-use change in the Amazon Basin - Lanji Ma; Jiaxue Wang; Yujiao Wei; Peiheng Yu; Yongsheng Hong; Zihao Wu; Yaolin Liu; Gan-Lin Zhang; José A.M. Demattê; Budiman Minasny; Yiyun Chen (CATENA, 2026)

Dynamic analysis of an eccentrically loaded rigid strip footing on transversely isotropic unsaturated soils - Gan Lin Gu; Zhi Yong Ai; Li Wei Shi (Soil Dynamics and Earthquake Engineering, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Immune dysregulation and cellular dysfunction mediate di-n-pentyl phthalate–induced hepatotoxicity: Insights from single-cell RNA sequencing - Yu Gan; Yongyi Luo; Xiandong Ye; Kaiyan Zhang; Zhenqiu Xia; Lei Yang; Chaoming Zhou; Gan Xie; Wenyan Zhong; Tengfei Yuan; Shuimiao Lin; Yuan Fang; et al. (Food and Chemical Toxicology, 2026)

A microbial consortium for mariculture wastewater Treatment: Metabolic reprogramming ensures enhanced nitrogen and phosphorus removal under dynamic nutrient conditions - Chenyu Yang; Xiangying Yu; Bifu Gan; Xin Lin; Jing Zhao (Bioresource Technology, 2026)

From copper imbalance to immunometabolic remodeling: cuproptosis-related vulnerability and therapeutic hypotheses in autoimmune diseases - Yang Shao; Rui feng Zhang; Zhonghe Wang; Jiali Gan; Xi juan Jiang; Lin Yang; Zhi jie Song (Inflammation Research, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Atmospheric new particle formation from sulfuric acid-amine nucleation in a rural area of the North China Plain - Yiliang Liu; Yiqun Lu; Gan Yang; Chuang Li; Yuwei Wang; Runlong Cai; Lei Yao; Yang Chen; Lin Wang (Journal of Environmental Sciences, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Cross-country differences in consumer acceptance and advocacy of novel food technologies - Brian Lin; Denise Conroy; Amy Errmann; Caixia Gan; Hugo Fahn (Food Quality and Preference, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

Daily mortality prediction under compound environmental stressors: Comparing epidemiological time series models and machine learning models - Wanjie Wang; Xiaoyan Zhou; Na Li; Feng Chen; Jingqiao Fu; Zhiyang Su; Yuqing Yao; Xiaoyan Yuan; Sirui Lin; Mengfan Chen; Maji Gan; Jieming Zhong; et al. (Environmental Research, 2026)

Resource-efficient numerical computing and elastic wave behavior analysis in complex poroelastic media - Zhitao Zhang; Yuhang Guo; Zhuwen Wang; Baozhi Pan; Yibo Wang; Lin Gan; Wubing Wan; Zhaoqi Sun; Wenqiang Wang; Ruiyi Han; Jiaxu Guo; Yitong Cui (Computers and Geotechnics, 2026)

Multi-layer fluid-soil-structure interaction SPH modeling of suction bucket foundation installation process - Lin Gan; Hao Wang; Can Yi; Renji Gu; Dianlei Feng (Computers and Geotechnics, 2026)

Nonlinear unsaturated seepage analysis via Picard iteration and level-set method within the scaled boundary finite element framework - Chuhao Huang; Jun Liu; Lei Gan; Wenbin Ye; Peiqing Wang; Xinwei Song; Gao Lin; Zhi liu (Computers and Geotechnics, 2026)

Constructed wetlands with recycled glass pumice as substrate: Application in eel recirculating aquaculture systems - Jinghong He; Jiemei Wang; Jinzhi Zou; Hoi Leong Lee; Yanan Chen; Qiaodan Gan; Rongtai Lin; Junlv Chen; Ding Yuan; Yuhao Zhou (Chemical Engineering Journal, 2026)

In-situ heterojunction on high-aspect-ratio cellulose nanocrystals for long-range charge transport in e-skin - Chenchen Shen; Weiwei Chen; Lin Guo; Yanrui Zou; Shuan Han; Ning Yu; Lin Gan; Jin Huang (Carbohydrate Polymers, 2026)

Circular bioprocessing of bovine blood for peptide-based antimicrobial and antibiofilm agents - Gan Huey; Asif Ali Bhat; Bao-Hong Lee; Ming‐Kuei Shih; Li-Jung Yin; You-Lin Tain; Yu-Wei Chen; Yeu-Ching Shi; Chih-Yao Hou (Bioresource Technology, 2026)

Experimental Investigation into the Influence of Water Saturation on the Tensile Failure Behavior of Diaspore-Type Bauxite: Implications for Underground Mining of Bauxite - Defu Zhu; Wenshuo Hu; Yalin Li; Qingsheng Bai; Yongjie Jia; TengFei Fu; Gan Feng; Yujiang Zhang; Xiaosong Sun; Yongqing Lin; Dingwei Sun (Rock Mechanics and Rock Engineering, 2026)

Correction to: FOXK2/SH2D3A axis recruits EGFR to drive papillary thyroid cancer progression and confers sensitivity to EGFR inhibition - Qin Cui; Xulin Hong; Lin Gan; Bimin Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

FOXK2/SH2D3A axis recruits EGFR to drive papillary thyroid cancer progression and confers sensitivity to EGFR inhibition - Qin Cui; Xulin Hong; Lin Gan; Bimin Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Multi-strain Bacillus Probiotics has Advantages in Improving Abnormal Behavior and Intestinal Flora in Rats of Autism Spectrum Disorder - Qi-qi Bai; Ji Chen; Lu-lu Dong; Mei-lin Jin; Bo-kai Hu; Yu Gan; Chen-ye You; Jing Hui (Current Microbiology, 2026)

A one-tube RAA-PfAgo system for rapid and sensitive detection of Monkeypox virus - Na Zhao; Xuejian Zhang; Yulu Gan; Lin Li; Yunmin Wang; Tong Xu; Yao Pan; Kui Gu; Yu Zhao (Analytica Chimica Acta, 2026)

Monitoring soil heavy metal content around a lead–zinc mining area in Yunnan, China using GF-5A and Sentinel-2B remote sensing with consideration of pollution sources - Lin Hu; Jiankai Hu; Shu Gan; Xiping Yuan; Jie Li; Yingtao Qi; Chengzhuo Lu (International Journal of Remote Sensing, 2026)

Hydraulic performance of circular tunnels with interior drainage boundaries subjected to water level fluctuation - Hao-Ran Lai; Dong-Mei Zhang; Yi-Yao Shen; Bin-Lin Gan (Transportation Geotechnics, 2026)

A machine learning-based soft sensor for monitoring PPCPs removal in wastewater treatment plants - Lin Gan; Ji Li; Zhizhang Shen (Journal of Environmental Chemical Engineering, 2026)

Geometry-matched chelation enhances Li+ diffusion on electrodes binded by modified carboxymethyl cellulose - Zi Ye; Xi Yang; Wenhan Chen; Xinye Li; Yu Chen; Ning Yu; Jin Huang; Lin Gan (Carbohydrate Polymers, 2026)

Beyond Borders: Tracking Water and Carbon Footprints of Global Transport Modes - Chenglong Wang; Xuewei Guo; Chenyang Shuai; Xi Chen; Wei Huang; Lin Gan; Jingran Sun; Bu Zhao (Water Resources Management, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

InceptionFormer: A deep learning framework for UAV LiDAR point cloud completion to improve tree parameters estimation in dense forests - Binhan Luo; Jian Yang; Shuo Shi; Ruilin Gan; Zhongliang Wu; Sihao Wang; Ao Wang; Lin Du; Wei Gong (Remote Sensing of Environment, 2026)

Numerical investigation and entropy-based assessment of connectivity and permeability in 3D fracture networks - Lei Tian; Litang Hu; Jianchong Sun; Lin Gan (Engineering Geology, 2026)

Engineering a temperature-programmable biosensor toolkit for recombinant protein production in Corynebacterium glutamicum - Haofei Xu; Yanbo Li; Yiran Gan; Songzhou Liu; Bin Lin; Shijun Cen; Yankun Yang; Chunli Liu; Xiuxia Liu; Zhonghu Bai (Systems Microbiology and Biomanufacturing, 2026)

Environmental factors shape the intestinal microbiota and function of Manila clam Ruditapes philippinarum - Bifu Gan; Guiling Li; Yanru Xu; Jingmiao Yang; Weilang Lin; Xiaobo Yan; Maozi Lin; Guangmao Ding; Fang Su; Qizhen Xiao (Frontiers in Marine Science, 2026)
Intestinal microbiota of aquatic animals is closely associated with the environment, influencing their health, immune defense, and environmental adaptability. To understand the relationships among the Manila clam ( Ruditapes philippinarum ) intestinal microbiota, the bacterial communities in their habitats, and environmental factors, as well as the characteristics and potential functions of the intestinal microbiota. This study systematically analyzed the bacterial communities in the clam intestines, seawater, and sediment samples from two typical habitats using 16S rRNA gene (V3-V4) sequencing. The results revealed significant differences in bacterial community composition among the intestines, seawater and sediment, with pronounced regional variations also evident within the same sample type. The clams gut microbiota in Fuqing was predominantly composed of Alphaproteobacteria , Gammaproteobacteria , Bacteroidota , Bacillota , and Cyanobacteria . In Putian, Cyanobacteria comprised an exceptionally high proportion. However, Bacillota , Bacteroidota , and Actinomycetota showed similar relative abundances in both regions, indicating a potential “core bacterial community”. Regarding the α-diversity of gut microbiota, although no significant differences were observed between clam samples from the two regions, their diversity was significantly lower than that of the sediment bacterial communities. The intestinal bacterial communities exhibited high similarity to the aquatic bacterial communities in terms of richness, diversity, and dominant species abundance, and it shares most of the ASVs with the sediment, suggesting that environmental microorganisms may serve as the primary source of the clam intestinal microbiota. Environmental drivers of bacterial communities differed regionally. In Fuqing, bacterial communities were associated with temperature, DO, pH, and salinity, and exhibited broader niche widths; in Putian, they were mainly influenced by nutrients, showing narrower niches. Compared to bacterial networks in the environment, the interactions among members within the gut bacterial communities of clams display modularity, indicative of functional specialization. The composition and functions of the intestinal microbiota of clams vary significantly in different environments, which may be a manifestation of their ecological adaptability. The composition and function of clam intestinal microbiota varied with environment, reflecting their ecological adaptability. These findings provide a scientific theoretical basis for water quality regulation and disease prevention in aquatic animal farming operations.

Integrated electricity‒heat scheduling optimization strategy for biomass-PV-battery islanded microgrid with micro turbine in high-latitude regions - Gong Wang; Ke Dong; Yuanhua Song; Shengxian Cao; Liuming Gao; Mingli Yu; Hao Gan; Chuanjie Lin; Guichao Duan; Huijing Sun (Biomass and Bioenergy, 2026)

Research progress on NSP4 protein of porcine reproductive and respiratory syndrome virus - Xiaolin Lan; Fang Liang; Gan Li; Yaqiong Ye; Feng Li; Chen Lv; Kexin Liu; Zhiyu Yang; Ruyu Sun; Keshan Zhang; Lin Wang; Huawei Li; et al. (Veterinary Research Communications, 2026)

Improved methods for assessing summer thermal environments in tropical urban beaches: Combining field measurements and simulation - Jiahao Yang; Zhaosong Fang; Shaolin Gan; Jiacheng Wen; Xiang Zhang; Yini Fan; Zhiyi Huang; Yuyang Lin; Jun Lu (Building and Environment, 2026)

circSCAP-encoded SCAP-129aa mediates platinum resistance in triple-negative breast cancer via the PI3K/AKT pathway - Qi Wang; Yudong Li; Zhuangqiu Yang; Wang Yang; Yujie Liu; Liang Jin; Shunying Li; Qianfeng Shi; Zijie Cai; Yiye Ouyang; Mengzi Wu; Ruiquan Liu; et al. (Science China Life Sciences, 2026)

Drier year exhibits amplified promoting effects of shrub encroachment on methane uptake in Tibetan alpine meadows - Lili Nan; Zelong Zhang; Dezhao Gan; Huinan Li; Dongsheng Yu; Zhenrong Lin; Zheng Li; Jian Hu; Hui Wang; Qingping Zhou; Shuli Niu; Jinsong Wang; et al. (Agricultural and Forest Meteorology, 2026)

The role of KPNA3 in multiple myeloma: implications for targeting nuclear import - Hongmei Luo; Ziyue Mi; Jingcao Huang; Jingjing Wen; Siyao He; Haonan Yang; Yue Zhang; Linfeng Li; Xiang Liu; Xinyu Zhai; Fangfang Wang; Xinai Gan; et al. (Apoptosis, 2026)

Design strategies based on hydrological performance of bioretention: experiments and modeling - Luwen Zhuang; Jianliang He; Jingmao Zhang; Gang Hu; Han Zhu; Wenhui Gan; Kairong Lin (Journal of Hydrology, 2026)

Real-world VOCs from ethanol gasoline vehicles: Speciation, ozone formation potential, and inter-city differences - Ziyang Zhang; Jing Li; Jun Li; Hairong Cheng; Haibin Huang; Jianchu Ma; Boji Lin; Gan Zhang (Journal of Hazardous Materials, 2026)

Effect of palladium loading on catalytic performance and product selectivity during diclofenac degradation by Pd0@anaerobic activated sludge - Xiaodi Li; Jingzhou Zhou; Lin Yang; Si Pang; Yi Yang; Defu Gan; Junxia He; Penghui Shi; Siqing Xia (Journal of Cleaner Production, 2026)

Adsorption mechanism of hydrogen bromide and 2-bromophenol on CuO, Cu2O, α-Fe2O3, and NiO catalysts: A density functional theory study - Lushi Sun; Jiaxing Du; Tao Chen; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Chemical Engineering, 2026)

Fe-modified CoS2/ZnIn2S4 heterojunction for dual-driven photoactivation of peroxymonosulfate: Efficient degradation of antibiotics in water - Xiao Feng; Qiqi Gan; Zhongliang Li; Yunhong Zhao; Tengfeng Xie; Dejun Wang; Yanhong Lin (Journal of Environmental Chemical Engineering, 2026)

Maternal prenatal mercury exposure from rice and its association with newborn neurobehavioral development - Chunfang Gan; Xinbin Feng; Kun-Lin Yang; Guangyi Sun; Weijun Luo; Qiang Yang; Wenjin Zhang; Yan Shi; Li Wang; Min Xiong; Mahmoud A. Abdelhafiz (Environmental Pollution, 2026)

Synergistic effects of amendments and Vetiveria zizanoides on soil quality and heavy metal bioavailability in a historical mine site: A 2-year field evaluation - Xiaolong Lan; Wenjie Lin; Jiaqi Li; Yin Li; Yaqi Zhao; Yili Gan; Yanlong Jia; Zengping Ning; Tangfu Xiao; Enzong Xiao (Ecological Engineering, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Emerging graphitic carbon nitride-based piezocatalysts for multifunctional applications: Environmental remediation, renewable energy and antibacterial technology - Yaping Gan; Shuqi Li; Khan Khalid; Gebrehiwot Gebreslassie; Mengru Li; Abera Beyene Gebresilassie; Xuezhi Liu; Lianjun He; Bin Lin (Chemical Engineering Journal, 2026)

Flexible poly(1,3-dioxolane) ether in oriented-porous and two-stage modified nanocellulose for ionization/transport dual-improved quasi-solid polymeric electrolyte - Xi Yang; Wenhan Chen; Zi Ye; Zhengxia Yu; Kejie Huang; Ning Yu; Jin Huang; Lin Gan (Carbohydrate Polymers, 2026)

Effects of Straw Returning on Physicochemical Properties and Microbial Characteristics of Agricultural Soil - Tantan Zhang; Shiqiang Ge; Rong Gan; Siyuan He; Fuyuan Duan; Lin Li (Current Microbiology, 2026)

Quantitative source apportionment of deep nitrate in a typical black soil critical zone: Vertical partitioning and legacy effects in Northeast China - Shunhua Yang; Yue Dong; Yonghui Shi; Huayong Wu; Xiaodong Song; Gan-Lin Zhang (Agriculture, Ecosystems & Environment, 2026)

Associations of air pollution and genetic risk and their interaction with risk of Alzheimer’s disease: identification of risk loci and potential biological pathways - Shanshan Ran; Jingyi Zhang; Miao Cai; Lan Chen; Zhengmin Qian; Fei Tian; Gan Wu; Ri’enna Boyd; Stephen Edward McMillin; Huai-cai Zeng; Yin Yang; Hualiang Lin (GeroScience, 2026)

Molecular identification and population genetic analysis of a three-way cross hybrid abalone - Haichen Zhang; Qizhen Xiao; Weihong Lin; Zekun Huang; Benben Miao; Yang Gan; Chengyun Li; Caihuan Ke; Xuan Luo; Weiwei You (Aquaculture, 2026)

mTOR mediates airway epithelial E-cadherin disruption in toluene diisocyanate-induced asthma - Lin Fu; Lichang Chen; Xianru Peng; Changyun Yang; Jiamin Sun; Zemin Chen; Sudan Gan; Shiyue Li; Haixiong Tang; Yidan Lin; Lihong Yao (Toxicology and Applied Pharmacology, 2026)

Distinct links between climate warming, mariculture activities, and coastal benthic ecosystem change - Yong Xu; Jixing Sui; Lin Ma; Jinbao Wang; Qi Kou; Zhibin Gan; Lin Gong; Mei Yang; Qingxi Han; Xinzheng Li; Dong Dong (Journal of Environmental Management, 2026)

Exploring the nonlinear and spatial effects of urban activity heterogeneity on the nighttime thermal environment using machine learning and GWR - Jingyi Lin; Wei Gan; Xiang Li; Xiaochi Xu (Building and Environment, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

The Role of HIF-1α/BNIP3 Pathway in Hippocampal Neuronal Autophagy in Epilepsy - Huimin Kuang; Youshi Meng; Xinran Qin; Kai Qian; Chi Gong; Sijun Li; Lin Zhang; Xiaohang Gan; Yuling Lu; Yuan Wu (Molecular Neurobiology, 2026)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Soil inorganic carbon variations and thresholds of occurrence in an arid and semi-arid zone - Jin Hu; Xiao-Dong Song; Fei Yang; Shun-Hua Yang; Jin-Ling Yang; Gan-Lin Zhang (Geoderma Regional, 2025)

Flexible bifunctional electrode with a record-breaking ΔE = 0.55 V for fast charging fiber zinc-air batteries - Long Jiang; Yumin Chen; Jing Zhou; Huangjian Chen; Yunzhan Ying; Shikun Liang; Yulong Wan; Shifan Zheng; Ju Lin; Yuyuan Yao; Lihua Gan; Lie Wang (Chemical Engineering Journal, 2025)

A new 2-arylbenzofuran derivative and other constituents from Smilax china L. and their chemotaxonomic significance - Li-Juan Hu; Xian-Sheng Ye; Kuan Lin; Jie Gao; De-Sen Yang; Guo-Ping Gan; Xi-Ji Shu; Wei Liu; You-Hua Yang (Biochemical Systematics and Ecology, 2025)

Inhibitors of NADH–O-methylquinone compound a class of antitubercular drugs - Dongzi Lin; Cheng Xu; Changyou Gan; Bihua Ou; Fengxian Luo; Zhigang She; Lei Zhou; Zhenhua Chen (Molecular Diversity, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Early Carboniferous Magmatic Rocks in Eastern Myanmar: Implications for the Tethyan Evolution - San Win; Qinglai Feng; Ye Myint Swe; Tianyu Zhao; Zhengqin Gan; Xiaomei Nie; Aung Khaing; Sai Naing Lin Aung (Journal of Earth Science, 2025)

Poroelastodynamic response of three-dimensional transversely isotropic seabed with anisotropic permeability under nonlinear waves - Gan Lin Gu; Zhi Yong Ai (Ocean Engineering, 2025)

Bending behaviour of rigid-flexible combined inflatable membrane structures for floating bridge modules - Yunling Ye; Jin Gan; Huabing Liu; Weiguo Wu; Lin Wang; Junyu Guo; He Li (Ocean Engineering, 2025)

Comparative analysis of dynamic response behavior between welded stud and demountable bolt connectors in steel-UHPC composites - Zhenyu Huang; Yu Zhou; Yingwu Zhou; Gan Lin (Engineering Structures, 2025)

A dynamic prediction model for maximum lateral displacement of foundation pit enclosure structure using multi-source fusion method - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu; Hong Wei Huang; Zeng Zhi Qian; Da Xing Zhou; Yu Xin Zhai; Hai Feng Guo (Computers and Geotechnics, 2025)

Biodiversity Buffers Phytoplankton Biomass Production Against Nanoparticle Pollution Through Increased Facilitation - Yiping Zuo; Qianna Xu; Michael Southard; Guangxing Zhang; Lan Gan; Hao Zhang; Pu Yan; Louis Walls; Mary Steinbeck; Muhan Zhao; Yongsheng Chen; Lin Jiang (Ecology Letters, 2025)
Although biodiversity is widely recognised for its role in maintaining ecosystem functioning under environmental change, its importance has received relatively little attention in the context of emerging environmental stressors such as nanoparticles. By assembling phytoplankton communities across a gradient of species richness and exposing them to varying concentrations of copper oxide nanoparticles, we experimentally explored how biodiversity modulates ecosystem functioning under nanoparticle exposure. We found that the positive effect of biodiversity on phytoplankton biomass production was amplified at higher nanoparticle concentrations, allowing diverse communities to maintain biomass despite strong inhibitory effects of nanoparticles on monocultures. This enhanced biodiversity effect was primarily driven by increased complementarity, specifically through more frequent facilitative interactions among species under nanoparticle stress. Our findings advance the understanding of how biodiversity preserves ecosystem functioning and underscore its role in mitigating the impacts of emerging anthropogenic stressors.

Influence of synthesis variables on the physicochemical properties of lignin-derived cryogels for levulinic acid production from oil palm mesocarp fiber - Nadiah Syafiqah Mohd Azlan; Chiew Lin Yap; Yong Wei Tiong; Suyin Gan; Mohd Basyaruddin Abdul Rahman (Journal of Environmental Chemical Engineering, 2025)

Investigation on the use of waste biomass as a carbonaceous reducing agent in industrial silicon smelting: Thermogravimetric analysis, cooperative behavior and reaction characteristic - Chenguang Han; Zhengjie Chen; Wenhui Ma; Lin Wang; Xiaowei Gan (Journal of Environmental Chemical Engineering, 2025)

Characteristics of atmospheric reduced-sulfur compounds at a suburban site of Shanghai - Kai Deng; Juntao Huo; Yuwei Wang; Lihong Wang; Sijia Yin; Chuang Li; Yueyang Li; Gan Yang; Lei Yao; Qingyan Fu; Lin Wang (Journal of Environmental Sciences, 2025)

Differential electric field homogenization postponed dendrite formation of zinc anodes at limiting current for long-life aqueous zinc batteries - Yin Yang; Xin Chen; Jingying Li; Jia Yao; Yi Gan; Junjie Zheng; Luyang Ge; Lin Lv; Li Tao; Jun Zhang; Hanbin Wang; Hao Wang; et al. (Chemical Engineering Journal, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

Moisture-mediated freeze-thaw degradation in bamboo from cellulose hydration to macroscale fracture - Jian Gan; Yahui Zhang; Qiuqin Lin; Wenji Yu (Carbohydrate Polymers, 2025)

Liquefaction-induced ground failure and structural damage following the March 28, 2025 M 7.9 Myanmar earthquake - Longwei Chen; Shengcong Gan; Lin Xiao; Wenqi Zhang; Siyi Suo; Xiaoli Xie; Xiaoyang Wu; Wenhua Qi; Yongzhi Wang; Duguo Wang (Earthquake Engineering and Engineering Vibration, 2025)

Development of single nucleotide polymorphisms markers associated with disease resistance towards Pseudomonas koreensis in empurau (Tor tambroides) using T-Plex ARMS PCR assay - Melinda Mei Lin Lau; Hung Hui Chung; Cindy Jia Yung Kho; Han Ming Gan; Azham Zulkharnain (Aquaculture International, 2025)

Lactucin enhances glucose uptake and glycolysis in C2C12 myotubes by activating AMPK signaling pathway - Hao Zheng; Kaiwen Kang; Yujia Zhang; Ligen Lin; Lishe Gan (Natural Product Research, 2025)

Ontology-driven knowledge graph for decision-making in resilience enhancement of underground structures: Framework and application - Bin-Lin Gan; Dong-Mei Zhang; Zhong-Kai Huang; Fei-Yu Zheng; Rui Zhu; Wei Zhang (Tunnelling and Underground Space Technology, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

Enhancing high-temperature phase stability and thermal properties of 5RE(TaxNb1-x)O4 high-entropy ceramics through chemical bonding strength optimization - Mengdi Gan; Liping Lai; Xiaoyu Chong; Qianqian Jin; Wei Yu; Jiankun Wang; Jun Wang; Lin Chen; Jingjin He; Jing Feng (Chemical Engineering Journal, 2025)

Cellulose nanocrystal-modified hydrogel wearable sensor with self-healing function from dynamic bond and controllable dual hydrogen-bond crosslinking - Ruihuan Gu; Weiwei Chen; Yanrui Zou; Tingting Yang; Zirui Liu; Ning Yu; Jin Huang; Lin Gan (Carbohydrate Polymers, 2025)

Linking Water Technologies with Water Practices: Case Studies from 11 Countries - Lin Gan; Yongping Wei; Shuanglei Wu (Water Resources Management, 2025)
Radical transformations of technology development are required to meet the rapidly increasing global water resource challenges. A systemic understanding of the impacts of water technologies on water practices across countries remains limited. This paper aims to develop an understanding of the linkages between water technologies and water practices in the 11 countries where 95% of the world’s water patents were produced. The water technological development was assessed by both the contents (different types of technologies) and the structure (the technology network). The water practices were presented by country-level indicators representing their water demand, water supply, and water management collected from public databases. It was found that there was an extremely uneven distribution with the top 3 countries (China, Korea, Japan) accounting for over 70% of the total patents, and there were slow growth rates and even a decline of water technologies. All countries demonstrated homogeneous technological development focusing on water supply, and their networks had limited brokerage capacity for knowledge diffusion. Australia, China, Canada, France, and Korea had relatively good links between water technologies and practices, whereas the majority of countries demonstrated unbalanced technological structures with a de-linking to water practices. These findings can assist in developing water technologies for improving water practices in future.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Contact-dependent antagonism is mediated by a T7SSb toxin effector–immunity protein pair via ADP-ribosylation - Hongxin Guan; Huan Wu; Mengrou Gan; Jing Zhang; Jiajun Wang; Siyao Liu; Shuyue Chen; Yindi Jiao; Fan Li; Shiqing Huang; Sihuang Lin; Hongwei Chen; et al. (Science Bulletin, 2025)

Interface molecular reconstruction with scarcity active factor for long-life aqueous zinc batteries at thermal environment - Xin Chen; Yin Yang; Runzhi Liang; Junjie Zheng; Jia Yao; Jingying Li; Yi Gan; Xin Liu; Xiaodong Liang; Ze Wang; Qin Liu; Lin Lv; et al. (Chemical Engineering Journal, 2025)

Spatial confinement-enabled full-color emission from carbon dots via controlled sp2 domain assembly in spray pyrolysis - Lin Lan; Zhenfeng Gan; Yuan Ma; Rui Bao; Xin Kong; Liang Liu; Jianhong Yi (Chemical Engineering Journal, 2025)

Traffic-based resilience assessment on urban road tunnel affected by fire accident - Rui Zhu; Dong-Mei Zhang; Zhong-Kai Huang; Xiao-yang Guo; Bin-lin Gan; Wen-ding Zhou (Tunnelling and Underground Space Technology, 2025)

Adult children's education and elderly parents' energy poverty: Evidence from China - Hongwu Gan; Chuan Lin; Yang Zhou; Zhiyi Zhuo (Energy Policy, 2025)

Predicting steady-state seepage flow in complex half-space using a modified scaled boundary finite element method - Chuhao Huang; Jun Liu; Zhiqiang Hu; Lei Xiong; Zhi Liu; Lei Gan; Wenbin Ye; Gao Lin (Computers and Geotechnics, 2025)

Airborne Microplastic Pollution in a Highly Urbanized City: Occurrence, Characteristics, Human Exposure and Potential Risks - Yijing Gan; Xinlu Yang; Lixiang Zhong; Xinyan Chen; Mingfu Lin; Xian Qing; Laiguo Chen; Jun Wang; Yumei Huang (Water, Air, & Soil Pollution, 2025)

Rodent Bioturbation Significantly Enhances Annual Methane Uptake by Tibetan Alpine Grasslands - Dezhao Gan; Dongsheng Yu; Hongchao Zuo; Zheng Li; Zelong Zhang; Huinan Li; Zhenrong Lin; Hui Wang; Qingping Zhou; Jinsong Wang; Shuli Niu; Ruijun Long; et al. (Global Change Biology, 2025)
Tibetan alpine grasslands (AG) serve as critical methane (CH 4 ) sinks, yet face degradation from anthropogenic and climatic disturbances that promote subterranean rodents (e.g., Plateau zokor [ Myospalax baileyi ] and pika [ Ochotona curzoniae ]) activities. Although rodent bioturbation (e.g., burrowing, foraging and excreting) alters soil structure, soil physico‐chemical properties and productivity from AG, its impacts on CH 4 uptake remain poorly understood. Among the first, we combined paired year‐round CH 4 flux measurements from Plateau zokor mounds (ZM) and surrounding healthy meadow (HM) patches in Tibetan alpine meadow with collated CH 4 fluxes from meta‐ and synthetic analyses across Tibetan AG, temperate grasslands (TG) and tropical grasslands (TrG) globally. We observed that rodent bioturbation significantly ( p 4 uptake (HM: −0.91 ± 0.08 kg C ha −1 vs. ZM: −1.80 ± 0.19 kg C ha −1 , mean ± standard error, negative values indicate uptake). Notably, 67% of this net increase (−0.89 ± 0.10 kg C ha −1 year −1 ) due to rodent bioturbation occurred during the growing season. Meta‐analysis results revealed this phenomenon associated with significantly ( p pmoA for methanotrophs. Non‐growing season (NGS) CH 4 uptake contributed 45% and 39% to annual CH 4 uptake for HM and ZM, respectively, falling into the ranges of 12%–64% NGS CH 4 uptake contributions from TG to AG of China. The TrG showed significant ( p 4 uptake than TG and AG globally, due to the fact that significant ( p 4 flux changes and highlight soil moisture as a key driver for global CH 4 sink variations. These results emphasise the need for long‐term monitoring to better assess the ecological consequences of bioturbation in climate‐sensitive alpine ecosystems.

Performance analysis of Timoshenko beams on transversely isotropic porous subgrade due to moving loads considering thermal effects - Zhi Yong Ai; Li Wei Shi; Gan Lin Gu; Xiao Ming Wang (Soil Dynamics and Earthquake Engineering, 2025)

A deep learning model based on data decomposition and modern convolution for predicting influent characteristics of wastewater treatment plant - Lin Gan; Ao Li; Ji Li; Zhizhang Shen (Journal of Water Process Engineering, 2025)

Decoding the nexus of surface water and groundwater in Northwestern China: Insights from long-term irrigation activities and numerical modeling - Lin Gan; Litang Hu; Zhongjing Wang; Na Zhang; Guiyu Yang; Suyue Yu (Journal of Hydrology, 2025)

Element mobilization characteristics and environmental impact of flowback water during fracturing fluid-shale interaction at different time scales - Qipan Liu; Yue Ni; Yong Lei; Huanhuan Zhao; Yashi Liu; Lin Gan; Zepeng Sun (Journal of Environmental Chemical Engineering, 2025)

Mercury migration characteristics and the re-emission inhibition in seawater flue gas desulfurization system - Chuanwei Li; Gan Wan; Linlin Xu; Jiaxing Du; Lushi Sun; Li Lin (Journal of Environmental Chemical Engineering, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

The role of electroactive biofilms in enhanced para-chlorophenol transformation collaborated with biosynthetic palladium nanoparticles - Shaofeng Zhou; Yanjing Li; Shan Yang; Lizhou Lin; Tongchu Deng; Cuifen Gan; Wenwen An; Meiying Xu (Environmental Pollution, 2025)

A genome-wide association study of growth traits in “Green Pacific hybrid abalone” (Haliotis discus hannai ♀ × H. fulgens ♂) - Yanyu Yao; Linyue Wang; Lu Li; Xu Lin; Zhen Zhao; Hanling Gan; Yilei Wang; Ziping Zhang (Aquaculture, 2025)

Self-replenishing neutral Fenton-like treatment for emerging contaminants through single Fe atom electron configuration regulation - Wen-Min Wang; Wen-Long Wang; Lin Gan; Yuxiong Huang; Danmeng Shuai; Min-Yong Lee; Qian-Yuan Wu (Water Research, 2025)

Spatial distributions, driving factors, and threshold effects of soil organic carbon stocks in the Tibetan Plateau - Zheng Sun; Feng Liu; Fei Yang; Decai Wang; Gan-Lin Zhang (Soil and Tillage Research, 2025)

Uncertainty analysis of 3D post-failure behavior in landslide and reinforced slope based on the SPH method and the random field theory - Dianlei Feng; Lin Gan; Min Xiong; Weile Li; Yu Huang (Engineering Geology, 2025)

Electrochemical oxidation of methylene blue from high salinity dyeing wastewater by a novel reduced graphene oxide and La co-modified PbO2 electrode - Zepeng Sun; Lin Gan; Yashi Liu; Qipan Liu; Qian Gao; Yue Ni (Desalination, 2025)

Low-frequency ultrasound-driven piezoelectric films repair neuro-immune circuits in diabetic wound healing - Chenyan Yu; Ying Hu; Xin Zhang; Kaixu Yu; Lang Chen; Wenqian Zhang; Shengming Zhang; Zhenhe Zhang; Ruiyin Zeng; Yuheng Liao; Yanzhi Zhao; Lin Gan; et al. (Chemical Engineering Journal, 2025)

A state-of-the-art empirical round robin validation of heat, air and moisture (HAM) models - Xinyuan Dang; Ana Sofia Guimarães; Andreas Sarkany; Anssi Laukkarinen; Bingyu Xu; Bruno Vanderschelden; Carsten Rode; Changchang Xia; Chi Feng; Chris Whitman; Daan Deckers; Hanyu Yang; et al. (Building and Environment, 2025)

Organic fertilizer application reduce ammonia volatilization in an acidic soil - Cai Gan; Yanbin Jiang; Yan Wang; Shan Lin; Yue Luo; Huabin Li; Yunwei Li; Niannian Tang; Yang Fei; Ronggui Hu (Agriculture, Ecosystems & Environment, 2025)

Assessing geological structure uncertainties in groundwater models using transition probability-based realizations - Shiqi Huang; Litang Hu; Binghua Li; Xia Wu; Lin Gan; Jianchong Sun; Menglin Zhang (Journal of Hydrology, 2025)

The dewatering performance of streptomycin mycelial residue promoted by the Fenton process synergistic with biochar - Lushi Sun; Jiaxing Du; Xingxing Zhou; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Management, 2025)

Nitrogen-removed organic matters from cyanobacterial decomposition promote the release of nitrogen from lake sediment - Mengmeng Wang; Yixuan Zhan; Chenyu Wang; Xiaohua Song; Lin Gan; Hao Lu; Liuyan Yang (Environmental Science and Pollution Research, 2025)

Effects of hormones and digestive tract morphology on personality-driven foraging behaviour in the turtle Mauremys reevesii - Lin Gan; Jiahui Sun; Hong Li (Animal Behaviour, 2025)

Coupling CO2 capture process with electrochemically enhanced membrane distillation system for lithium-ion battery recovery: Reagent-Saving and environmental footprint reducing - Longjie Jiang; Lin Chen; Chuqing Cao; Kang Chen; Chuhang Ji; Yi Zhang; Fangqun Gan (Water Research, 2025)

Mercury (II) adsorption and gaseous mercury re-emission inhibition from seawater flue gas desulfurization (SFGD) wastewater by Fe-Cu bimetallic modified activated carbon - Lushi Sun; Gan Wan; Ke Tang; Linlin Xu; Li Lin (Fuel, 2025)

Ultrathin surface-amination-modified membrane with ion-charge shielding effect for ultraselective nanofiltration - Qiangqiang Song; Yuqing Lin; Ning Gan; Hussain Sadam; Yaguang An; Zheng Wang; Kecheng Guan; Junyong Zhu; Jing Wang; Yatao Zhang; Hideto Matsuyama (Desalination, 2025)

Plant diversity increases diversity and network complexity rather than alters community assembly processes of leaf-associated fungi in a subtropical forest - Jie Li; Xing-Chun Li; Hui-Yun Gan; Yue Zhang; Zi-Xuan Guo; Yu-Xuan Liu; Yong-Qing Lin; Liang-Dong Guo (Science China Life Sciences, 2025)

Transcriptome analysis reveals the dynamics of gene expression during early embryonic development of hybrid groupers - Fengying Yan; Chongwei Wang; Yuzhi Zhu; Jinhui Wu; JiayuYang; Songyong Gan; Hao Ran Lin; Yong Zhang; Shuisheng Li (Aquaculture, 2025)

Polarized electric field induced by piezoelectric effect of ozone micro-nano bubbles/spontaneously polarized ceramic to boost ozonolysis for efficient fruit sterilization - Xiangxuan Lin; Wuxiang Zhang; Jie Xiong; Zuqiang Huang; Tao Gan; Huayu Hu; Yuben Qin; Yanjuan Zhang (Food Chemistry, 2025)

Mineral, molecular composition and ecosystem type jointly determine the stability of soil organic carbon on the Qinghai-Tibetan Plateau - Jun Gu; Dongxue Li; Fei Yang; Xiao-Dong Song; Ke-Yang Gong; Gan-Lin Zhang (CATENA, 2025)

Specific Mode Electroacupuncture Stimulation Mediates the Delivery of NGF Across the Hippocampus Blood–Brain Barrier Through p65-VEGFA-TJs to Improve the Cognitive Function of MCAO/R Convalescent Rats - Mengyuan Dai; Kecheng Qian; Qinyu Ye; Jinding Yang; Lin Gan; Zhaoxing Jia; Zixing Pan; Qian Cai; Tianxiang Jiang; Congcong Ma; Xianming Lin (Molecular Neurobiology, 2025)
Cognitive impairment frequently presents as a prevalent consequence following stroke, imposing significant burdens on patients, families, and society. The objective of this study was to assess the effectiveness and underlying mechanism of nerve growth factor (NGF) in treating post-stroke cognitive dysfunction in rats with cerebral ischemia–reperfusion injury (MCAO/R) through delivery into the brain using specific mode electroacupuncture stimulation (SMES). From the 28th day after modeling, the rats were treated with NGF mediated by SMES, and the cognitive function of the rats was observed after treatment. Learning and memory ability were evaluated using behavioral tests. The impact of SMES on blood–brain barrier (BBB) permeability, the underlying mechanism of cognitive enhancement in rats with MCAO/R, including transmission electron microscopy, enzyme-linked immunosorbent assay, immunohistochemistry, immunofluorescence, and TUNEL staining. We reported that SMES demonstrates a safe and efficient ability to open the BBB during the cerebral ischemia repair phase, facilitating the delivery of NGF to the brain by the p65-VEGFA-TJs pathway. Graphical Abstract By Figdraw

Impacts of Spartina alterniflora invasion on soil carbon components of particulate and mineral-associated organic matter and soil organic matter mineralization in estuarine wetlands - Lin Wang; Yuan Li; Jie Hei; Weiqi Wang; Jordi Sardans; Zhihao Zhang; Fanjiang Zeng; Maoquan Ge; Yiyang Liao; Yunying Fang; Tony Vancov; Jiawei Gan; et al. (Applied Soil Ecology, 2025)

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

Supramolecular-coordinated nanofiltration membranes with quaternary-ammonium Cyclen for efficient lithium extraction from high magnesium/lithium ratio brine - Ning Gan; Yuqing Lin; Baolong Wu; Yulong Qiu; Haopan Sun; Jingwen Su; Jianguo Yu; Qian Lin; Hideto Matsuyama (Water Research, 2025)

Harnessing metal-metal interactions for simultaneously boosting photocatalytic hydrogen and benzaldehyde production - Yajie Feng; Chi Lin; Yifei Huang; Bing Li; Yingxin He; Jiangping Ma; Chaogang Ban; Lujie Ruan; Hongxing Jia; Xiaoping Tao; Liyong Gan; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Enhancing electromechanical conversion and motion-monitoring application of pore-oriented cellulose nanocrystal/agarose aerogel modified with flexible heterojunction structures - Weiwei Chen; Lin Gan; Jie Xiong; Ga Liu; Tingting Yang; Yanrui Zou; Zhicheng Zhang; Jin Huang (Carbohydrate Polymers, 2025)

Unveiling a novel mechanism: Reduction of graphene oxide by Lysinibacillus sp. through secretion of l-ascorbic acid - Yuanyuan Zhou; Ziyi Lin; Yonghe Han; Li Gan; Ying Cheng; Zuliang Chen (Chemosphere, 2024)

A multi-omics approach reveals low temperature inhibition of flavones and flavonols accumulation in postharvest bananas via downregulation of MabHLH363 - Wen Song; Shu-Qin Lin; Qi Yin; Tian-He Liu; Lin-Zhi Gan; Jian-Ji Qi; Ying-Ying Yang; Wei Wei; Wei Shan; Jian-Fei Kuang; Jian-Ye Chen; Wang-Jin Lu (Postharvest Biology and Technology, 2024)

Polycyclic polyprenylated acylphloroglucinols from the pericarps of Garcinia multiflora champ. ex Benth. with cytotoxic property - Jun Cao; Wen-Yu Lyu; Yujia Zhang; Zhicheng Su; Ting Li; Qingwen Zhang; Lishe Gan; Jin-Jian Lu; Ligen Lin (Phytochemistry, 2024)

SILAR-assisted synthesis of Cu2O modified TiO2 nanotube arrays: Study on efficient photocatalytic dye degradation and hydrogen evolution - Junwei Hou; Lin Gan; Nan Bao; Chengye Zhang; Kailu Liu; Qingyao Wang (Journal of Water Process Engineering, 2024)

The improvement of gel properties and volatiles for frozen egg white melted assisted with ultrasound - Xiaole Xiang; Shiqin Dong; Le Chen; Yongle Liu; Yingqun Wu; Meijuan Yu; Gan Hu; Shugang Li; Lin Ye (Food Research International, 2024)

Dynamic interaction between continuously reinforced concrete pavement and fractional poroviscoelastic subgrade due to moving loading - Zhi Yong Ai; Xin Kai Chen; Xing Kai Wang; Gan Lin Gu (Computers and Geotechnics, 2024)

Alpha-ketoglutarate supramolecular network accelerates diabetic wound healing through exudates management and neovascularization - Yimeng Cai; Pochun Lin; Yuhan Li; Linfeng Liu; Shuqin Cao; Bin Zhao; Yueying Wang; Wei Song; Qian Wang; Xinyan Gan; Ke Xu; Qingheng Wu; et al. (Chemical Engineering Journal, 2024)

Graphics Processing Unit-Accelerated Propeller Computational Fluid Dynamics Using AmgX: Performance Analysis Across Mesh Types and Hardware Configurations - Yue Zhu; Jin Gan; Yongshui Lin; Weiguo Wu (Journal of Marine Science and Engineering, 2024)
Computational fluid dynamics (CFD) has become increasingly prevalent in marine and offshore engineering, with enhancing simulation efficiency emerging as a critical challenge. This study systematically evaluates the application of graphics processing unit (GPU) acceleration technology in CFD simulation of propeller open water performance. Numerical simulations of the VP1304 propeller model were performed using OpenFOAM v2312 integrated with the NVIDIA AmgX library. The research compared GPU acceleration performance against conventional CPU methods across various hardware configurations and mesh types (tetrahedral, hexahedral-dominant, and polyhedral). Results demonstrate that GPU acceleration significantly improved computational efficiency, with tetrahedral meshes achieving over 400% speedup in a 4-GPU configuration, while polyhedral meshes reached over 500% speedup with a fixed mesh count. Among the mesh types, hexahedral-dominant meshes performed best in capturing flow field details. The study also found that GPU acceleration does not compromise simulation accuracy, but its effectiveness is closely related to mesh type and hardware configuration. Notably, GPUs demonstrate more significant advantages when handling large-scale problems. These findings have important practical implications for improving propeller design processes and shortening product development cycles.

Mechanism of JNK action in oxidative stress–enhanced gut injury by Clostridium perfringens type A infection - Hailan Lin; Yifan Liu; Ling Zhang; Fan Yang; Yanqing Liu; Yuhang Li; Yuxuan Liu; Zhiyun Qiu; Hongyue Chen; Daoling He; Yan Zhu; Ling Gan (Veterinary Microbiology, 2024)

Deep nitrate accumulation in typical black soil critical zones of Northeast China - Shunhua Yang; Yue Dong; Mingyu Song; Jun Gu; Yonghui Shi; Huayong Wu; Xiaodong Song; Jinling Yang; Decheng Li; Gan-Lin Zhang (Science of The Total Environment, 2024)

Microplastics and biochar interactively affect nitrous oxide emissions from tobacco planting soil - Feier Wang; Hongguang Cheng; Shan Lin; Gratien Twagirayezu; Hengbin Xiao; Cai Gan; Jinli Hu; Yan Wang; Ronggui Hu (Science of The Total Environment, 2024)

Associations of ambient air pollution with incidence and dynamic progression of atrial fibrillation - Junguo Zhang; Linna Luo; Ge Chen; Baozhuo Ai; Gan Wu; Yanhui Gao; Gregory Y.H. Lip; Hualiang Lin; Yangxin Chen (Science of The Total Environment, 2024)

The spatial variations and driving factors of C, N, P stoichiometric characteristics of plant and soil in the terrestrial ecosystem - Wen-Lan Feng; Jin-Ling Yang; Li-Gang Xu; Gan-Lin Zhang (Science of The Total Environment, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

Advanced pyro-/piezoelectric catalytic disinfection of water via porous spontaneously polarized ceramic with strong local electric field induced by micro-nano bubbles - Wuxiang Zhang; Jie Xiong; Xiangxuan Lin; Yiping Liu; Tao Gan; Huayu Hu; Zuqiang Huang; Yanjuan Zhang (Chemical Engineering Journal, 2024)

OsNAC15 regulates drought and salt tolerance in rice - Chuan-Wei Ao; Gan-ju Xiang; Yan-Fei Wu; Yue Wen; Zhong-Lin Zhu; Feng Sheng; Xuezhu Du (Physiology and Molecular Biology of Plants, 2024)

The influences of ApoE isoforms on endothelial adherens junctions and actin cytoskeleton responding to mCRP - Zhengrong Zhang; Weiwei Lin; Qini Gan; Maohua Lei; Bin Gong; Chao Zhang; Jessica Salles Henrique; Jingyan Han; Hua Tian; Qiushan Tao; Lawrence A. Potempa; Thor D. Stein; et al. (Angiogenesis, 2024)

Allicin Ameliorated High-glucose Peritoneal Dialysis Solution-induced Peritoneal Fibrosis in Rats via the JAK2/STAT3 Signaling Pathway - Linwang Gan; Lei Geng; Qiancheng Li; Liling Zhang; Yan Huang; Jiaru Lin; Santao Ou (Cell Biochemistry and Biophysics, 2024)

Reconstructing high-resolution gridded precipitation data in the southwest China highland canyon area using an improved (MGWR) downscaling method - Lihong Wang; Yuechen Li; Yushi Gan; Long Zhao; Lei Fan; Wei Qin; Lin Ding (Science of The Total Environment, 2024)

First insight of the intergenerational effects of tri-n-butyl phosphate and polystyrene microplastics to Daphnia magna - Xiaoli Chen; Yijing Gan; Xinlu Yang; Lixiang Zhong; Menghuan Zhang; Mingfu Lin; Xian Qing; Jun Wang; Yumei Huang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Investigation of aerodynamic noise distribution characteristics on cruise ship open decks using broadband noise source models - Yue Zhu; Jin Gan; Yongshui Lin; Li Ma; Weiguo Wu (Ocean Engineering, 2024)

Numerical and experimental studies on flow characteristics and wind comfort assessment for the open decks of a cruise ship - Yue Zhu; Jin Gan; Li Ma; Xiliang Feng; Ziyang Liu; Yongshui Lin; Weiguo Wu (Ocean Engineering, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Wind erosion prevention and trans-boundary ecosystem service payments in the Hunshandake region - Mengdong Huang; Yu Xiao; Changshun Zhang; Lin Zhen; Keyu Qin; Jingya Liu; Jie Xu; Shuang Gan; Jia Liu; Chunxia Lu; Gaodi Xie (Journal of Cleaner Production, 2024)

Preparation of pH sensitive P-doped carbon dots-loaded starch/polyvinyl alcohol packaging film for real-time monitoring freshness of pork - Jie Ding; Xiufen Liao; Wanhe Li; Xiangxuan Lin; Huayu Hu; Yanjuan Zhang; Tao Gan; Zuqiang Huang (Food Bioscience, 2024)

Polystyrene shell-based “coconut-like” and “pomegranate-like” microencapsulated phase change materials: Formation mechanism, thermal conductivity/stability enhancement and their application in thermal management - Wei Zhang; Rui Pan; Jihua Yang; Mengru Liu; Yunle Yao; Awang Zhang; Yi Gong; Zhengya Gan; Rui Hu; Jianjun Ding; Lin Chen; Xian Zhang; et al. (Chemical Engineering Journal, 2024)

pH and redox dual-responsive ZIF-8-based nanoplatform for targeted pathogens and environmental protection - Shuhui Hu; Lin-Lin Yang; Chang Yan; Yanan Xiao; Zijing Jin; Xiuhai Gan; Bo Zhang; Wenneng Wu (Chemical Engineering Journal, 2024)

WITHDRAWN: Chondroitin sulfate modulates oxidative stress and inflammation in the substantia nigra via gumicrobiota regulation: Mechanistic insights into Parkinson's disease treatment - Lin Gan; Peng Yu; Kunyu Wang; Wei Jiang; Yuxin Fu; Ming Dong (Carbohydrate Polymers, 2024)

Immobilization of laccase on mesoporous metal organic frameworks for efficient cross-coupling of ethyl ferulate - Xinqi Xu; Feng Shen; Gan Lv; Juan Lin (World Journal of Microbiology and Biotechnology, 2024)

Plasma-derived exosomal miRNA profiles reveal potential epigenetic pathogenesis of premature ovarian failure - Jiaqiong Lin; Zhihong Wu; Yingchun Zheng; Zongrui Shen; Zhongzhi Gan; Shunfei Ma; Yanhui Liu; Fu Xiong (Human Genetics, 2024)

Hydrochemical insights, water quality, and human health risk assessment of groundwater in a coastal area of southeastern China - Yanhong Zheng; Denghui Wei; Jie Gan; Lin Zou; Rilong Zhu; Yunhui Zhang (Environmental Monitoring and Assessment, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Edaphic regulation of soil organic carbon fractions in the mattic layer across the Qinghai-Tibetan Plateau - Jun Gu; Fei Yang; XiaoDong Song; ShunHua Yang; Gan-Lin Zhang (Science of The Total Environment, 2024)

Microplastic co-exposure elevates cadmium accumulation in mouse tissue after rice consumption: Mechanisms and health implications - Shan Chen; Haijun Gan; Xinying Lin; Boxuan Wang; Mengya Li; Lena Q. Ma; Dongmei Zhou; Hongbo Li (Journal of Hazardous Materials, 2024)

Microbiomes on microplastics versus natural microcarriers: Stability and transformation during aquatic travel from aquaculture ponds to adjacent stream - Lizhou Lin; Youda Huang; Weibin Jia; Shaofeng Zhou; Cuifen Gan; Wei-Min Wu; Meiying Xu (Journal of Hazardous Materials, 2024)

Ternary stabilization strategies for succinonitrile-based in situ polymerized electrolyte enabling high-performance solid lithium metal batteries - Chenyu Lin; Tianqi Yang; Haiyuan Zhang; Donghuang Wang; Wenkui Zhang; Yao Wang; Yang Xia; Hui Huang; Xinhui Xia; Yongping Gan; Xinping He; Xinyong Tao; et al. (Chemical Engineering Journal, 2024)

Heparin mimicking sulfonated polyester synergistically promotes bacterial Infected-Wound healing with ROS responsive cinnamaldehyde based prodrugs - Haiwei Liu; Pengfei Shan; Yingwen Lu; Xiaoyue Lian; Feng He; Jinxiang Xiao; Linan Qiu; Zhenghao Liu; Zuobin Gan; Qingshan Yan; Yupeng Qiu; Wenwen Lin; et al. (Chemical Engineering Journal, 2024)

Effects of disposable face mask microplastics on soil properties and microbial communities - Liping Lin; Gongren Hu; Yangzi Lijin; Luowei Gan; Ruiqi Zhang; Ling Wang; Changhao Lu; Jianping Gao; Jiatai Lin; Le Yang; Yu Yan; Ruilian Yu (CATENA, 2024)

Thermostatic microwave-assisted pretreatment of corn stover at atmospheric pressure to enhance saccharification - Lihong Wang; Jinghua Fan; Lihui Gan; Xianhai Zeng; Lu Lin; Jian Liu (Biomass and Bioenergy, 2024)

Dual-carbon isotope analysis of benzene polycarboxylic acids for tracking black carbon across different environments - Xin Yi; Guangcai Zhong; Xiaofei Geng; Jiao Tang; Boji Lin; Sanyuan Zhu; Shutao Gao; Chuxin Yao; Zhineng Cheng; Shizhen Zhao; Jun Li; Gan Zhang (Applied Geochemistry, 2024)

Corrigendum to “Polystyrene nanoplastics cause reproductive toxicity in zebrafish: PPAR mediated lipid metabolism disorder” [Sci. Total Environ. 931(2024):172795] - Yi Zheng; Xiufeng Gan; Chengyin Lin; Danhan Wang; Runyu Chen; Yuqing Dai; Lemiao Jiang; Changjiang Huang; Ya Zhu; Yang Song; Jiangfei Chen (Science of The Total Environment, 2024)

A novel identification model for rock burst grades-taking Jinping II hydropower station hub engineering as an example - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu (Computers and Geotechnics, 2024)

Structuring restricted amorphous molecular chains in the reinforced cellulose film by uniaxial stretching - Jing Wang; Shi-Peng Chen; De-Long Li; Lin Zhou; Jia-Xin Ren; Li-Chuan Jia; Gan-Ji Zhong; Hua-Dong Huang; Zhong-Ming Li (Carbohydrate Polymers, 2024)

Research Overview on Sugarcane Deep Processing and Comprehensive Utilization in China - Gan-Lin Chen; Jing Chen; Bo Lin; Ling-Zhi Zhao; Feng-Jin Zheng; Krishan K. Verma; Yang-Rui Li (Sugar Tech, 2024)

Genome-wide CRISPR screening identifies critical role of phosphatase and tensin homologous (PTEN) in sensitivity of acute myeloid leukemia to chemotherapy - Liming Lin; Jingjing Tao; Ying Meng; Yichao Gan; Xin He; Shu Li; Jiawei Zhang; Feiqiong Gao; Dijia Xin; Luyao Wang; Yili Fan; Boxiao Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Metabolic engineering of Saccharomyces cerevisiae for high-level production of (+)-ambrein from glucose - Chumin Lin; Xiaopeng Zhang; Zhongju Ji; Baolian Fan; Yaman Chen; Yuhong Wu; Yuhong Gan; Zhengping Li; Yi Shang; Lixin Duan; Feng Wang (Biotechnology Letters, 2024)

A simple numerical simulation model can elucidate the key factors for designing a miniaturized ion trap mass spectrometer - Xinming Huo; Lin Gan; Xinyue Ding; Quan Yu; Bin Zhou; Jianhua Zhou; Xiang Qian (Analytica Chimica Acta, 2024)

Flexible self-powered bioelectronics enables personalized health management from diagnosis to therapy - Guang Yao; Xingyi Gan; Yuan Lin (Science Bulletin, 2024)

Low temperature downregulates MabHLH355 and its associated target genes responsible for scavenging ROS in banana peel under cold stress - Shu-Qin Lin; Wen Song; Lin-Zhi Gan; Wei Wei; Wei Shan; Jian-Fei Kuang; Jian-Ye Chen; Wang-Jin Lu (Postharvest Biology and Technology, 2024)

Biogenic palladium nanoparticles for wastewater treatment: Formation, applications, limitations, and future directions - Xiaodi Li; Lin Yang; Jingzhou Zhou; Ben Dai; Defu Gan; Yi Yang; Zhenyu Wang; Junxia He; Siqing Xia (Journal of Water Process Engineering, 2024)

Corrigendum to “Quantification and variation characteristics of baseflow nonpoint source pollution in Yiluo River Basin, China” [J. Hydrol. 626(Part B) (2023) 130303] - Jiake Zheng; Rong Gan; Xiaoxia Tong; Lin Guo; Hui Tang; Jie Tao (Journal of Hydrology, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Optimized DLP 3D-printed high-resolution nano zirconia-hydroxyapatite scaffold with craniomaxillofacial soft tissue invasion resistance and pro-osteogenic properties via dectin-1/syk inflammatory axis - Xiaomeng Gao; Jieting Yang; Xuejing Gan; Yixiong Lin; Jieyun Xu; Zhengjie Shan; Zongpu Han; Shijie Chen; Baoxin Huang; Bingfeng Fan; Zetao Chen (Chemical Engineering Journal, 2024)

Polystyrene nanoplastics cause reproductive toxicity in zebrafish: PPAR mediated lipid metabolism disorder - Yi Zheng; Xiufeng Gan; Chengyin Lin; Danhan Wang; Runyu Chen; Yuqing Dai; Lemiao Jiang; Changjiang Huang; Ya Zhu; Yang Song; Jiangfei Chen (Science of The Total Environment, 2024)

DPABINet: A toolbox for brain network and graph theoretical analyses - Chao-Gan Yan; Xin-Di Wang; Bin Lu; Zhao-Yu Deng; Qing-Lin Gao (Science Bulletin, 2024)

Hidden danger: The long-term effect of ultrafine particles on mortality and its sociodemographic disparities in New York State - Quan Qi; Fangqun Yu; Arshad A. Nair; Sam S.S. Lau; Gan Luo; Imran Mithu; Wangjian Zhang; Sean Li; Shao Lin (Journal of Hazardous Materials, 2024)

Formation mechanism of polycyclic aromatic hydrocarbons during mineral oil pyrolysis: A ReaxFF molecular dynamics study - Linlin Xu; Gan Wan; Lushi Sun; Li Lin (Fuel, 2024)

A lychee fermentate with enriched acetate but lowered GABA attenuates DSS-induced colitis by reinforcing gut barrier function and modulating intestinal microbiota - Rui Huang; Hong Yao; Suying Ji; Junfeng Wu; Qingran Lin; Tanushree B. Gupta; Dan Gan; Xiyang Wu (Food Bioscience, 2024)

Role of rainfall temporal distribution on effective infiltration in the loess slope and prediction model - Gan Lin; Hengxing Lan; Ping Li; Langping Li; Shijie Liu; Weifeng Sun (Engineering Geology, 2024)

Spatial identification and evaluation of rural vitality from a function-element-flow perspective: Evidence of Lin’an district in Hangzhou, China - Jing Zhang; Chenyue Guan; Lin Zhang; Zhoulu Yu; Chengxuan Ye; Congmou Zhu; Sinan Li; Ke Wang; Muye Gan (Journal of Geographical Sciences, 2024)

In situ green immobilization of palladium nanoparticles onto polydopamine-modified eggshell membrane for catalytic reduction of nitrophenols - Yi Yang; Defu Gan; Xiaodi Li; Jingzhou Zhou; Lin Yang; Ben Dai; Siqing Xia (Journal of Water Process Engineering, 2024)

Contrasting impacts of fertilization on topsoil and subsoil greenhouse gas fluxes in a thinned Chinese fir plantation - Qingyan Qiu; Chi Ding; Abubakari Said Mgelwa; Jiguang Feng; Mei Lei; Ziying Gan; Biao Zhu; Ya-lin Hu (Journal of Environmental Management, 2024)

Developing a national black soil map of China through machine learning classification - Zheng Sun; Feng Liu; Huayong Wu; Gan-Lin Zhang (CATENA, 2024)

The role of JAK2/STAT3 pathway in non-cytotoxic concentrations of DON-induced aggravation of inflammatory response in IL-10 deficient RAW264.7 cells - Junya Zeng; Ziman Lin; Jiangyu Tang; Xingxiang Chen; Kehe Huang; Fang Gan (Food and Chemical Toxicology, 2024)

Air pollution, APOE genotype and risk of dementia among individuals with cardiovascular diseases: A population-based longitudinal study - Fei Tian; Zhengmin Qian; Zilong Zhang; Yuewei Liu; Gan Wu; Chongjian Wang; Stephen Edward McMillin; Elizabeth Bingheim; Hualiang Lin (Environmental Pollution, 2024)

Humoral immunosuppression of exposure to polycyclic aromatic hydrocarbons and the roles of oxidative stress and inflammation - Yingyi Dai; Qianyun Deng; Qiaojuan Liu; Lin Zhang; Huiquan Gan; Xinhong Pan; Bing Gu; Lei Tan (Environmental Pollution, 2024)

Push-out test behavior and damage detection of steel-UHPC composite using PZT sensing - Xiaolong Zhao; Gan Lin; Yingwu Zhou; Zhenyu Huang (Engineering Structures, 2024)

Effects of forest thinning on soil microbial biomass and enzyme activity - Hongwei Xu; Quan Gan; Lulu Huang; Xingyu Pan; Tongwei Liu; Ruiyang Wang; Limengjie Wang; Li Zhang; Han Li; Lixia Wang; Sining Liu; Jiao Li; et al. (CATENA, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Detection and analysis of landslide geomorphology based on UAV vertical photogrammetry - Rui Bi; Shu Gan; Xiping Yuan; Kun Li; Raobo Li; Weidong Luo; Cheng Chen; Sha Gao; Lin Hu; Zhifu Zhu (Journal of Mountain Science, 2024)

Upgrading swin-B transformer-based model for accurately identifying ripe strawberries by coupling task-aligned one-stage object detection mechanism - Huan Liu; Xiaoxuan Wang; Feiyu Zhao; Feiyang Yu; Ping Lin; Yang Gan; Xuefeng Ren; Yongming Chen; Jian Tu (Computers and Electronics in Agriculture, 2024)

MicroRNA-194-5p/Heparin-binding EGF-like growth factor signaling mediates dexamethasone-induced activation of pseudorabies virus in rat pheochromocytoma cells - Chen Zhang; Yuxuan Liu; Fan Yang; Yifan Liu; Naixiu Wang; Yuhang Li; Yanqing Liu; Zhiyun Qiu; Lin Zhang; Xiaoyan You; Ling Gan (Veterinary Microbiology, 2024)

Nitrate leaching characteristics of red soils from different parent materials in subtropical China - Yue Dong; Jin-Ling Yang; Xiao-Rui Zhao; Shun-Hua Yang; Gan-Lin Zhang (Science of The Total Environment, 2024)

Demystifying the interconnections among natural resources, fintech, green technologies, and sustainable environment in E-7 nations - Hsiao-Hsien Lin; Chao-Chun Hsu; Po-Hsuan Wu; Chih-Chien Shen; Gan-Hong Chen (Resources Policy, 2024)

Thermo-hydro-mechanical coupled responses of layered transversely isotropic saturated media under moving thermal and mechanical loads - Zhi Yong Ai; Gan Lin Gu; Xiao Ming Wang (Computers and Geotechnics, 2024)

Fabrication of biodegradable and cold-water-soluble starch/polyvinyl alcohol films as inner packaging materials of pesticides: Enhanced emulsification, dispersibility, and efficacy - Jia Song; Xiangxuan Lin; Hongrui Wu; Zuqiang Huang; Tao Gan; Huayu Hu; Yuben Qin; Yanjuan Zhang (Carbohydrate Polymers, 2024)

Occurrence of leaf spot caused by Colletotrichum plurivorum on cowpea in Fujian Province, China - Yuli Dai; Lin Gan; Xiaofei Liu; Chengzhong Lan; Zhiqiang Li; Xiujuan Yang (Crop Protection, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

A comparative metabolomics study on two fresh edible lilies for vegetable: Lilium brownii var. viridulum and Lilium davidii var. unicolor - Lu Mi; Kewen Wang; Zhilin Gan; Yuhong Lin; Xue Wang; Shuming Yang; Zhenzhen Xu (Food Bioscience, 2024)

Black phosphorus nanosheets inhibit glioblastoma cell migration and invasion through modulation of WNT/β-catenin and NOTCH signaling pathways - Yue Xiong; Chao He; Xun Lin; Ke Cheng; Fumei He; Jingxin Zhao; Mengjie Yang; Hong Gao; Fangjie He; Xiaopei Zhang; Zeqi Liu; Gan Liu; et al. (Chemical Engineering Journal, 2024)

Enhanced microwave conversion of oil palm mesocarp fiber to levulinic acid using H3PW12O40-Nb2O5 functionalized carbon cryogel derived from lignin hydrogel - Nadiah Syafiqah Mohd Azlan; Chiew Lin Yap; Yong Wei Tiong; Suyin Gan; Mohd Basyaruddin Abdul Rahman (Bioresource Technology Reports, 2024)

Sorting Technology for Mesenchymal Stem Cells from a Single Tissue Source - Xinyi Feng; Fangfang Qi; Hailin Wang; Wenzhen Li; Yuyang Gan; Caiyu Qi; Zhen Lin; Lu Chen; Piao Wang; Zhiqi Hu; Yong Miao (Stem Cell Reviews and Reports, 2024)

Corrigendum to “Leaf hydraulic distance is a good predictor of growth within and across conifer species in a Taiga ecosystem” [AgriculturalandForestMeteorology342(2023)109710] - Xingyue Li; Dayong Fan; Zhengxiao Liu; Zengjuan Fu; Changqing Gan; Zeyu Lin; Chengyang Xu; Han Sun; Xiangping Wang (Agricultural and Forest Meteorology, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Crucial physicochemical factors mediating mitochondrial toxicity of nanoparticles at noncytotoxic concentration - Ze Zhang; Gan Miao; Lin Lu; Hao Yin; Yingzhu Wang; Baoqiang Wang; Ruonan Pan; Chuer Zheng; Xiaoting Jin (Science of The Total Environment, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Ammonium intercalation engineering regulated structural stability of V6O13 cathodes for durable zinc ion batteries - Ziang Wu; Jia Yao; Chi Chen; Xiang Chen; Xiaoxin Pan; Junjie Zheng; Yi Gan; Jingying Li; Xingtai Liu; Chao Xia; Lin Lv; Hao Wang; et al. (Chemical Engineering Journal, 2024)

Micro assembly strategies for enhancing solid-state emission of cellulose nanocrystals and application in photoluminescent inks - Zhenxu Shi; Dimei Yang; Yan Zhou; Xinyu Chen; Lin Gan; Jin Huang (Carbohydrate Polymers, 2024)

Rainfall erosivity index for monitoring global soil erosion - Lihong Wang; Yuechen Li; Yushi Gan; Long Zhao; Wei Qin; Lin Ding (CATENA, 2024)

Cell size‐dependent species sensitivity to nanoparticles underlies changes in phytoplankton diversity and productivity - Yiping Zuo; Michael Southard; Qianna Xu; Guangxing Zhang; Emily Skibinski; Nicole Moon; Lan Gan; Yongsheng Chen; Lin Jiang (Global Change Biology, 2024)
Nanoparticle pollution has been shown to affect various organisms. However, the effects of nanoparticles on species interactions, and the role of species traits, such as body size, in modulating these effects, are not well‐understood. We addressed this issue using competing freshwater phytoplankton species exposed to copper oxide nanoparticles. Increasing nanoparticle concentration resulted in decreased phytoplankton species growth rates and community productivity (both abundance and biomass). Importantly, we consistently found that nanoparticles had greater negative effects on species with smaller cell sizes, such that nanoparticle pollution weakened the competitive dominance of smaller species and promoted species diversity. Moreover, nanoparticles reduced the growth rate differences and competitive ability differences of competing species, while having little effect on species niche differences. Consequently, nanoparticle pollution reduced the selection effect on phytoplankton community abundance, but increased the selection effect on community biomass. Our results suggest cell size as a key functional trait to consider when predicting phytoplankton community structure and ecosystem functioning in the face of increasing nanopollution.

Depth profiles of microplastics in sediments from inland water to coast and their influential factors - Bing Yuan; Wenhui Gan; Jian Sun; Binliang Lin; Zhihe Chen (Science of The Total Environment, 2023)

Exploring the potential of magnetic persimmon tannins-based bio-adsorbent for Cd (II) ions removal from water: Experiment and DFT study - Fan Zhou; Lin Gao; Shunyan Cui; Jing Tian; Tong Wang; Guiyin Li; Zhongmin Wang; Chaoke Qin; Dahong Lin; Weijiang Gan; Zhaojin Ran (Journal of Water Process Engineering, 2023)

Environmental exposure disparities in ultrafine particles and PM2.5 by urbanicity and socio-demographics in New York state, 2013–2020 - Arshad Arjunan Nair; Shao Lin; Gan Luo; Ian Ryan; Quan Qi; Xinlei Deng; Fangqun Yu (Environmental Research, 2023)

Gas barrier coating based on cellulose nanocrystals and its preservation effects on mango - Mingxia Li; Zhenxu Shi; Shulin He; Qiang Hu; Ping Cai; Lin Gan; Jin Huang; Yongqiang Zhang (Carbohydrate Polymers, 2023)

Somatic embryo induction and plantlet regeneration of Canna × generalis from immature zygotic embryo - Zu-yan Gan; Mu-lin Shu; Feng Yang; Guo-fang Wang; Wen-e Zhang; Xue-jun Pan (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Investigation of Effect of Wind-Induced Vibration on Typical Frame Structures on the Open Decks of Large Cruise Ships Based on the Subdomain Method - Xiliang Feng; Yue Zhu; Jin Gan; Ziheng Chen; Jing Li; Yongshui Lin; Weiguo Wu (Journal of Marine Science and Engineering, 2023)
Due to the tall and large superstructures of cruise ships, the wind-induced vibration of frame structure on open decks cannot be neglected. This study investigated the wind-induced vibration of a typical frame structure on a cruise ship by using wind tunnel tests and numerical simulations. Wind tunnel tests were conducted to explore the simulation methods of the fluid–structure interaction (FSI). CFD simulations were performed to obtain the wind field data of the entire ship, which was utilized as an input for the open deck through the subdomain method. Subsequently, wind-induced vibration simulations of the guide rail frame structure on the open deck was carried out under various wind conditions. The results revealed that employing the turbulence model SST k-ω had a good agreement with the experimental data. The entire ship’s CFD results have a significant impact on the subdomain’s wind-induced vibration results. The vibration frequency of the guide rail frame structure was mainly concentrated between 0.8–10.1 Hz. The most unfavorable conditions appear at the wind attack angles of 0° and 120°. This study can provide some instructive insights for the prediction of wind-induced vibration and control of typical structures on the open decks of large cruise ships.

Quantification and variation characteristics of baseflow nonpoint source pollution in Yiluo River Basin, China - Jiake Zheng; Rong Gan; Xiaoxia Tong; Lin Guo; Hui Tang; Jie Tao (Journal of Hydrology, 2023)

Green synthesis of bimetallic Pd Ag alloy nanoparticles supported on polydopamine-functionalized kaolin for catalytic reduction of 4-nitrophenol and organic dyes - Defu Gan; Zhenyu Wang; Xiaodi Li; Jingzhou Zhou; Ben Dai; Lin Yang; Siqing Xia (Applied Clay Science, 2023)

Leaf hydraulic distance is a good predictor of growth response to climate aridity within and across conifer species in a Taiga ecosystem - Xingyue Li; Dayong Fan; Zhengxiao Liu; Zengjuan Fu; Changqing Gan; Zeyu Lin; Chengyang Xu; Han Sun; Xiangping Wang (Agricultural and Forest Meteorology, 2023)

Improved ammonia emission inventory of fertilizer application for three major crops in China based on phenological data - Yongqi Zhao; Baojie Li; Jinyan Dong; Yan Li; Xueqing Wang; Cong Gan; Yingzhen Lin; Hong Liao (Science of The Total Environment, 2023)

Ambient air pollution associated with incident asthma, subsequent cardiovascular disease and death: A trajectory analysis of a national cohort - Xiaojie Wang; Shanshan Ran; Hui Xia; Hui Shi; Gan Wu; Zilong Zhang; Chongjian Wang; Miao Cai; Junguo Zhang; Hualiang Lin (Journal of Hazardous Materials, 2023)

Heat source model for Enhanced Geothermal Systems (EGS) under different geological conditions in China - Wenjing Lin; Guiling Wang; Haonan Gan; Shengsheng Zhang; Zhen Zhao; Gaofan Yue; Xiting Long (Gondwana Research, 2023)

A hybridized continuum-discontinuum modeling for investigating the fracture and energy evolution characteristics of rock mass under sequential explosive detonation using a bilinear cohesive fracture model - Qindong Lin; Xinguang Zhu; Jianfei Yuan; Chun Feng; Yundan Gan; Wenjun Jiao; Yulei Zhang (Computers and Geotechnics, 2023)

Removal of antibiotic-resistant bacteria and genes by Solar-activated Ferrate/ Peroxymonosulfate: Efficiency in aquaculture wastewater and mechanism - Ruixue Li; Xudai Wu; Zhenfei Han; Lijie Xu; Lu Gan; Yanqiong Zhang; Fengru Lu; Hua Lin; Xue Yang; Muting Yan; Wei Chu; Han Gong (Chemical Engineering Journal, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

Developing a novel Gaussian process model predictive controller to improve the energy efficiency and tracking accuracy of the pressure servo control system - Zhonglin Lin; Jinyu Gan; Qiang Qian; Feng Huang; Xinglong Zhang; Tianhong Zhang; Wenchao Liu (Journal of Cleaner Production, 2023)

Clinical and neonatal outcomes of using a modified micro cryotube for cryopreservation of small numbers of spermatozoa for TESA-ICSI cycles - Huanhua Chen; Ruoyun Lin; Zhulian Wu; Hong Zhou; Caizhu Wang; Xianyou Gan; Kongrong Xu; Kejian Sun; Xihe Deng; Jinhui Shu (Cryobiology, 2023)

Prediction of low Zn concentrations in soil from mountainous areas of central Yunnan Province using a combination of continuous wavelet transform and Boruta algorithm - Hailong Zhao; Shu Gan; Xiping Yuan; Lin Hu; Junjie Wang; Shuai Liu (International Journal of Remote Sensing, 2023)

Genome-wide association screening and MassARRAY for detection of high-temperature resistance-related SNPs and genes in a hybrid abalone (Haliotis discus hannai ♀ × H. fulgens ♂) based on super genotyping-by-sequencing - Zhen Zhao; Hanling Gan; Xu Lin; Linyue Wang; Yanyu Yao; Lu Li; Yilei Wang; Ziping Zhang (Aquaculture, 2023)

Analytical method for predicting tunnel heave due to overlying excavation considering spatial effect - Kang Cheng; Riqing Xu; Hongwei Ying; Cungang Lin; Xiaolu Gan; Xiaonan Gong; Jianfeng Zhu; Sijie Liu (Tunnelling and Underground Space Technology, 2023)

Soil acidification in a tailing area of ionic rare earth in Southeast China - Zhe Xu; Jin-ling Yang; Yue Zhao; Rui Hao; Gan-lin Zhang (Science of The Total Environment, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

Whole-Genome Sequencing of Pseudomonas koreensis Isolated from Diseased Tor tambroides - Cindy Jia Yung Kho; Melinda Mei Lin Lau; Hung Hui Chung; Ivy Yee Yen Chew; Han Ming Gan (Current Microbiology, 2023)

Ambient air pollution and incidence, progression to multimorbidity and death of hypertension, diabetes, and chronic kidney disease: A national prospective cohort - Gan Wu; Miao Cai; Chongjian Wang; Hongtao Zou; Xiaojie Wang; Junjie Hua; Hualiang Lin (Science of The Total Environment, 2023)

Overexpression of OsNF-YB4 leads to flowering early, improving photosynthesis and better grain yield in hybrid rice - Meifang Peng; Feng Gan; Xiaomin Lin; Run Yang; Shaoyi Li; Wei Li; Lan Wu; Xiaoli Fan; Kegui Chen (Plant Science, 2023)

RNA-Sequencing Reveals Gene Expression and Pathway Signatures in Umbilical Cord Blood Affected by Birth Delivery Mode - Yongjie Liu; Kun Sun; Yuexin Gan; Han Liu; Juehua Yu; Wei Xu; Lin Zhang; Dan Chen (Phenomics, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Amnion-derived serum amyloid A1 participates in sterile inflammation of fetal membranes at parturition - Yi-kai Lin; Fan Zhang; Wen-jia Lei; Xiao-wen Gan; Meng-die Li; Fan Pan; Wang-sheng Wang; Kang Sun (Inflammation Research, 2023)

Deep accumulation of soluble organic nitrogen after land-use conversion from woodlands to orchards in a subtropical hilly region - Shunhua Yang; Yue Dong; Huayong Wu; Xiaodong Song; Xiaorui Zhao; Jinling Yang; Gan-Lin Zhang (Science of The Total Environment, 2023)

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Mobile Phone Imaging Point Cloud Modelling for 3D Recording and Measurement of Small Scenes of Suspected Fossil Outcrops Found in the Field - Gao Sha; Gan Shu; Yuan Xiping; Hu Lin; Bi Rui; Li Raobo; Yang Ming (Geoheritage, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Creep characteristics of thermally-stressed Beishan granite under triaxial compression - Jian-Feng Liu; Xing Luo; Gan Feng; Lu-Lin Zhou; Xing-Guo Yang; Gong-Da Lu (International Journal of Rock Mechanics and Mining Sciences, 2023)

A conductive hydrogel based on nature polymer agar with self-healing ability and stretchability for flexible sensors - Zhen Nie; Kelin Peng; Lizhi Lin; Jueying Yang; Zhekun Cheng; Qiang Gan; Yu Chen; Changgen Feng (Chemical Engineering Journal, 2023)

An innovative passive sampler to reveal the high contribution of biomass burning to black carbon over Indo-China Peninsula: Radiocarbon constraints - Xiao Wang; Jun Li; Xiangyun Zhang; Zhineng Cheng; Haoyu Jiang; Hongxing Jiang; Boji Lin; Sanyuan Zhu; Shizhen Zhao; Junwen Liu; Chongguo Tian; Ruijie Zhang; et al. (Atmospheric Environment, 2023)

Marker-assisted breeding of rice lines special for rice noodle-making by pyramiding the Wxg2 and ALKGC genes - Bin Teng; Fengshun Song; Quan Gan; Cuixiang Lin; Dahu Ni (Euphytica, 2023)

Combined effects of prenatal phthalate exposure on cardiometabolic risk score among 4- to 7-year-old children: MABC study - Hui Gao; Meng-long Geng; Juan Tong; Bao-lin Wang; Kun Huang; Yi Zhang; Hong Gan; Bei-bei Zhu; Peng Ding; Qu-nan Wang; Jian-qing Wang; Cheng Zhang; et al. (Chemosphere, 2023)

Soil organic carbon content increase in the east and south of China is accompanied by soil acidification - Xiao-Lin Sun; Budiman Minasny; Yun-Jin Wu; Hui-Li Wang; Xiao-Hui Fan; Gan-Lin Zhang (Science of The Total Environment, 2023)

The effect of underwater supplemental light on the growth of V.spinulosa Yan and the restoration process of water - Jinshan Zhao; Pu Yang; Yuye Lin; Xiaoyao Zhu; Jiaxin Wang; Xinyu Gan; Xiangyong Zheng; Min Zhao; Chunzhen Fan; Linna Du; Huanyi Miu (Process Safety and Environmental Protection, 2023)

Removal of cadmium from wastewater using biofunctional reduced graphene oxide synthesized by Lysinibacillus sphaericus - Xiaoyu Lin; Li Gan; Gary Owens; Zuliang Chen (Journal of Cleaner Production, 2023)

Planar D-σ-A type thermally activated delayed fluorescence material with Intra- and intermolecular charge transfer characteristics - Simin Jiang; Jianyin Lin; Deli Li; Mengke Li; Yanmei He; Wentao Xie; Jiting Chen; Yiyang Gan; Guo-Xi Yang; Zhihai Yang; Wei Li; Shi-Jian Su (Chemical Engineering Journal, 2023)

Black phosphorus nanosheets suppress oxidative damage of stem cells for improved neurological recovery - Fumei He; Zeqi Liu; Jian Xu; Yue Xiong; Xiaopei Zhang; Junyang Qi; Xun Lin; Chengjun Chu; Lan Shen; Gan Liu; Wenbin Deng (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

First report of leaf blight on Panax notoginseng caused by Pestalotiopsis trachycarpicola in China - Cheng Zhong Lan; Xiong Lin; Yu Li Dai; Lin Gan; Xiao Fei Liu; Hong Chun Ruan; Xiu Juan Yang (Journal of Plant Pathology, 2022)

Prolonged electrolysis injures the neural development of zebrafish (Danio rerio) - Chaoqun Zheng; Yan Gao; Jinling Zhu; Lin Gan; Mengmeng Wang; Wen Zhang; Shunqing Yang; Liuyan Yang (Environmental Science and Pollution Research, 2022)

Recent development in zebrafish model for bioactivity and safety evaluation of natural products - Fang-Jun Lin; Hang Li; Ding-Tao Wu; Qi-Guo Zhuang; Hua-Bin Li; Fang Geng; Ren-You Gan (Critical Reviews in Food Science and Nutrition, 2022)

Knockdown of SOX9 alleviates tracheal fibrosis through the Wnt/β-catenin signaling pathway - Lei Gu; Anmao Li; Jing Lin; Yiling Gan; Chunyan He; Rui Xiao; Jiaxin Liao; Yishi Li; Shuliang Guo (Journal of Molecular Medicine, 2022)

HC-1119, a deuterated Enzalutamide, inhibits Migration, Invasion and Metastasis of the AR-positive triple-negative breast Cancer cells - Xuehong Wu; Wanru Feng; Mao Yang; Xunxi Liu; Mengdi Gao; Xinghai Li; Lin Gan; Tao He (Molecular Biology Reports, 2022)
Triple-negative breast cancers (TNBCs) are aggressive, and they develop metastasis at earlier stages, relapse more frequently, and exhibits poorer prognosis than other subtypes of breast cancer. Due to the lack of estrogen receptor for endocrine therapy and HER2 for targeted therapy, new targeted therapies for TNBCs are urgently needed. Enzalutamide is a second-generation androgen receptor (AR) inhibitor, and HC-1119 is a new synthetic deuterated enzalutamide. Owing to the isotope effect, HC-1119 has many advantages over enzalutamide, including slow metabolism, high plasma concentration and low brain exposure. However, the efficacy of HC-1119 in inhibition of AR function in triple-negative breast cancer (TNBC) has not been studied. In this study, we found high-level AR expression in both Hs578T and SUM159PT TNBC cell lines. Activation of AR by dihydrotestosterone (DHT) in both cell lines increased AR protein, induced AR-nuclear localization, enhanced cell migration and invasion in culture, and promoted liver metastasis in mice. Importantly, cotreatment with HC-1119 of these cells efficiently abolished all of these effects of DHT on both Hs578T and SUM159PT cells. These results indicate that HC-1119 is a very effective new second-generation AR antagonist that can inhibit the migration, invasion and metastasis of the AR-positive TNBC cells.

Evapotranspiration characteristics in extensive green roofs during dry periods: the influences of vegetation treatment, substrate characteristics, and water retention layer - Jiaqin Liu; Ankit Garg; Jun Wang; Lin Gan; Hao Wang; Shan Huang; Ming Ma; Guoxiong Mei (Arabian Journal of Geosciences, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Statistical study on the CSES radio occultation data and its quality control in electron density inversion - Shengfeng Gu; Chengkun Gan; Yun Qing; Jian Lin; Xiaomin Luo; Xuhui Shen; Jingnan Liu (GPS Solutions, 2022)

Comparative Transcriptomics of Gonads Reveals the Molecular Mechanisms Underlying Gonadal Development in Giant Freshwater Prawns (Macrobrachium rosenbergii) - Guang Yang; Zhendong Qin; Zhijie Lu; Rishen Liang; Lijuan Zhao; Gan Pan; Li Lin; Kai Zhang (Journal of Marine Science and Engineering, 2022)
The giant freshwater prawn, Macrobrachium rosenbergii, is a prawn that has economic significance throughout the world. It exhibits sex-related growth dimorphism, whereby the males grow significantly more rapidly than the females. Therefore, a study on the molecular regulatory mechanism, which underlies the sexual differentiation of M. rosenbergii, is of both scientific and commercial importance. However, a scarcity of genomic and transcriptomic resources severely limits our knowledge of the sexual differentiation mechanisms in M. rosenbergii. Here, transcriptome sequencing of several gonadic samples of males and females in M. rosenbergii was performed to investigate the molecular basis underlying gonadal development. Our results showed that 2149 unigenes presented as differentially expressed genes (DEGs) in the ovaries of females compared to the testes of males, which contained 484 down-regulated and 1665 up-regulated genes. Enrichment analysis of DEGs revealed many of these genes to be related to sexual differentiation and gonadal development. From our transcriptome analyses, and as confirmed by quantitative real-time PCR, male-related genes (Mrr, MRPINK, IR, IAGBP, TESK1, and dsx) in the testes were significantly up-regulated, and female-related genes (ERR, Sxl3, cyclinB, Dmrt99B, PPP2A, and ADCY9) in the ovaries were also significantly up-regulated. This indicates the potential role these genes play in the gonadal development of M. rosenbergii. Furthermore, multiple signal transduction pathways relating to gonadal maturation and spermatogenesis, including MAPK, were identified herein. Our data also supports previous ideas that IAG and IAGBP-IR signaling schemes could help in the regulation of testis’ development in M. rosenbergii and the ERR gene could regulate ovarian development by affecting the expression of cyclinB, PPP2A, and ADCY9. The data from this study provides incredibly usefully genomic resources for future research on the sexual differentiation and practical aquaculture of M. rosenbergii.

Nitrate runoff loss and source apportionment in a typical subtropical agricultural watershed - Yue Dong; Jin-Ling Yang; Xiao-Rui Zhao; Shun-Hua Yang; Jan Mulder; Peter Dörsch; Gan-Lin Zhang (Environmental Science and Pollution Research, 2022)

Distributions, origins, and health-risk assessment of nitrate in groundwater in typical alluvial-pluvial fans, North China Plain - Lin Gan; Guanxing Huang; Lixin Pei; Yanjing Gan; Chunyan Liu; Mingnan Yang; Dongya Han; Jiangmin Song (Environmental Science and Pollution Research, 2022)

Analysis of geomorphologic features of the circular structure in the south of Lufeng Dinosaur Valley - Hu Lin; Gan Shu; Yuan Xiping; Yang MingLong; Gao Sha; Bi Rui; Li Yan (Earth Science Informatics, 2022)

8- O - β -D-Glucopyranosyl-2-methylchromone, a new chromone glycoside from the Tibetan medicine plant of Swertia punicea Hemsl - Lin-Yun Mou; Min Wei; Hai-Yan Wu; Li-Jiao Hu; Jian-Long Li; Gan-Peng Li (Natural Product Research, 2022)

Effects of biochar on the growth of Vallisneria natans in surface flow constructed wetland - Chaoqun Zheng; Xuanwen Zhang; Lin Gan; Zhaofang He; Jinling Zhu; Wen Zhang; Yan Gao; Liuyan Yang (Environmental Science and Pollution Research, 2021)

Long-term changes of water acidity in an intact forested watershed in south China - Xiao-dong Liu; Ying-jie Feng; Qi-feng Mo; Guo-wei Chu; Yue-lin Li; Qian-mei Zhang; Wei-qiang Zhang; Xian-hua Gan; Qing Zhou (Journal of Mountain Science, 2021)

Retraction Note: Detection of PM2.5 in mountain air based on fuzzy multi-attribute and construction of folk sports activities - Guanming Liu; Lin Gan; Huailong Yang; Changyue Wang (Arabian Journal of Geosciences, 2021)

Influence of biochar amendment on stormwater management in green roofs: experiment with numerical investigation - Lin Gan; Ankit Garg; Hao Wang; Guoxiong Mei; Jiaqin Liu (Acta Geophysica, 2021)

Experimental study on the effect of temperature on marine clay consolidation with vertical sand drains - Qin-yang Sang; Yong-lin Xiong; Gan-bin Liu; Rong-yue Zheng (Marine Georesources & Geotechnology, 2021)

The Regulatory Relationships Between the Gonad-Inhibiting Hormone and Insulin-Like Androgenic Gland Hormone-Binding Protein Genes in the Eyestalk-Androgenic Gland-Testis Axis of Macrobrachium rosenbergii - Meizhen Tang; Zhijie Lu; Sarath V Babu; Guang Yang; Yanan Li; Zizheng Xu; Gan Pan; Zhendong Qin; Li Lin (Frontiers in Marine Science, 2021)
Gonad-inhibiting hormone (GIH) belongs to a family of neuropeptides that are released from the eyestalks of male crustaceans and plays key roles in gonadal maturity, reproduction, and molting. However, the detailed mechanisms underlying the effects of GIH on sexual regulation have yet to be elucidated. In the present study, we aimed to demonstrate how GIH mediate the activity of the androgenic gland (AG) to affect sexual regulation. To do this, we cloned and characterized a GIH sequence from Macrobrachium rosenbergii ( Mr GIH). The open reading frame (ORF) of Mr GIH was 360 bp and codes for a polypeptide of 119 amino acids and a putative protein of 13.56 KDa. Tissue analysis showed that Mr GIH is widely expressed in a range of tissues but particularly, the eyestalk, intestine, and nerve cord. Following the ds RNA silencing of Mr GIH for 24 h, the expression levels of Mr GIH were down-regulated in both the eyestalk and AG when compared with the negative control, but significantly increased the expression of Macrobrachium rosenbergii insulin-like androgenic gland hormone-binding protein ( Mr IAGBP) in AG, thus suggesting that Mr GIH is an inhibitory factor for Mr IAGBP. In addition, we found that eyestalk removal on certain days led to increased expression levels of Mr IAGBP expression. The expression levels of Mr IAGBP peaked at 2 d in the AG after unilateral and bilateral eyestalk ablation, exhibiting a 7.27- and 6.03-fold increase, respectively. Afterward, the expression of GIH protein levels were down-regulated and IAGBP protein levels were up-regulated after GIH silencing using immunohistochemistry method, combined with the increase of IAGBP protein levels after eyestalk ablation, confirming that Mr GIH is an inhibitory factor that can moderately regulate AG development and IAGBP expression. Collectively, our findings enriched the mechanisms that control the sexual regulation pathway of male M. rosenbergii , and provided significant information for further explorations of the mechanism underlying sex regulation in other decapod crustaceans.

Acute associations between air pollution on premature rupture of membranes in Hefei, China - Chao Zhang; Sha Li; Gan-lan Guo; Jing-wen Hao; Peng Cheng; Li-lin Xiong; Shu-ting Chen; Ji-yu Cao; Yu-wen Guo; Jia-hu Hao (Environmental Geochemistry and Health, 2021)

RETRACTED ARTICLE: Detection of PM2.5 in mountain air based on fuzzy multi-attribute and construction of folk sports activities - Guanming Liu; Lin Gan; Huailong Yang; Changyue Wang (Arabian Journal of Geosciences, 2021)

Local 3D scene fine detection analysis of circular landform on the southern edge of Dinosaur Valley - Gao Sha; Yuan Xiping; Gan Shu; Yang Milong; Hu Lin; Bi Rui (Arabian Journal of Geosciences, 2021)

Comparison of the Curative Effects of Hip Arthroplasty with Bio-Type Femoral Stem and Cemented Femoral Stem in Elderly Patients with Unstable Osteoporotic Intertrochanteric Femur Fractures - Xinxin Lin; Keqin Yang; Haitao Tan; Fengping Gan; Jianzhong Jiang (Journal of Medical and Biological Engineering, 2021)

Distribution, Risk Assessment, and Sources of Trace Metals in Surface Sediments from the Sea Area of Macao, South China - Cui Shi; Jianyao Chen; Lei Gao; Huayang Gan; Qiao Xue; Hai Lin (Archives of Environmental Contamination and Toxicology, 2021)

Performance of permeable pavement systems on stormwater permeability and pollutant removal - Zhiji Yu; Huihui Gan; Ming Xiao; Biao Huang; David Z. Zhu; Zheyun Zhang; Huanyan Wang; Yongliang Lin; Yonglong Hou; Shuai Peng; Wei Zhang (Environmental Science and Pollution Research, 2021)

PI3K/Akt/mTOR Signaling as Targets for Developing Anticancer Agents from Marine Organisms - Mingyue Guo; Ling Zuo; Gan Qiao; Minghua Liu; Shousong Cao; Xiukun Lin (Journal of Ocean University of China, 2021)

Stoichiometric relations of C, N, and P in urban top soils in Nanjing, China, and their biogeochemical implications - Jin-Ling Yang; Da-Gang Yuan; Yu-Guo Zhao; Yue He; Gan-Lin Zhang (Journal of Soils and Sediments, 2021)

Assimilation of Radar and Cloud-to-Ground Lightning Data Using WRF-3DVar Combined with the Physical Initialization Method—A Case Study of a Mesoscale Convective System - Ruhui Gan; Yi Yang; Qian Xie; Erliang Lin; Ying Wang; Peng Liu (Journal of Meteorological Research, 2021)

Phytolith evidence of water management for rice growing and processing between 8,500 and 7,500 cal years bp in the middle Huai river valley, China - Wuhong Luo; Yuzhang Yang; Lina Zhuang; Huiyuan Gan; Chunguang Gu; Chengqing Huang; Liugeng Lin; Juzhong Zhang (Vegetation History and Archaeobotany, 2021)

Model test on support scheme for carbonaceous slate tunnel in high geostress zone at high depth - Zhi-gang Tao; Shu-lin Ren; Gan Li; Hao-tian Xu; Sen-lin Luo; Man-chao He (Journal of Mountain Science, 2021)

Correction to: Hispanic Spinocerebellar Ataxia Type 35 (SCA35) with a Novel Frameshift Mutation - Chih-Chun Lin; Shi-Rui Gan; Deepak Gupta; Armin Alaedini; Peter H Green; Sheng-Han Kuo (The Cerebellum, 2021)

Report of epibenthic macrofauna found from Haima cold seeps and adjacent deep-sea habitats, South China Sea - Dong Dong; Xinzheng Li; Mei Yang; Lin Gong; Yang Li; Jixing Sui; Zhibin Gan; Qi Kou; Ning Xiao; Junlong Zhang (Marine Life Science & Technology, 2021)
This work reports on a preliminary taxonomic study of epibenthic macroinvertebrates collected or observed by underwater video at the Haima cold seeps and in adjacent deep-sea habitats, including a mud volcano field and Ganquan Plateau, during an expedition in the South China Sea by the Chinese-manned submersible Shenhai Yongshi in May 2018. A total of 41 species belonging to 6 phyla were identified, among which 34 species were collected from the Haima cold seeps. Mollusks and crustaceans that are specialized in reducing habitats were predominant in biotopes of the Haima cold seeps, whereas sponges and cold-water corals and their commensals were prominent in communities of the mud volcano field and the slopes of Ganquan Plateau. The distribution and faunal composition of each taxonomic group are discussed.

The involvement of α‐proteobacteria Phenylobacterium in maintaining the dominance of toxic Microcystis blooms in Lake Taihu, China - Jun Zuo; Lili Hu; Wei Shen; Jiaying Zeng; Lin Li; Lirong Song; Nanqin Gan (Environmental Microbiology, 2021)
Summary Lake Taihu in China has suffered serious harmful cyanobacterial blooms for decades. The algal blooms threaten the ecological sustainability, drinking water safety, and human health. Although the roles of abiotic factors (such as water temperature and nutrient loading) in promoting Microcystis blooms have been well studied, the importance of biotic factors (e.g. bacterial community) in promoting and meditating Microcystis blooms remains unclear. In this study, we investigated the ecological dynamics of bacterial community, the ratio of toxic Microcystis , as well as microcystin in Lake Taihu. High‐throughput 16S rRNA sequencing and principal component analysis (PCA) revealed that the bacteria community compositions (BCCs) clustered into three groups, the partitioning of which corresponded to that of groups according to the toxic profiles (the ratio of toxic Microcystis to total Microcystis , and the microcystin concentrations) of the samples. Further Spearman's correlation network showed that the α‐proteobacteria Phenylobacterium strongly positively correlated with the toxic profiles. Subsequent laboratory chemostats experiments demonstrated that three Phenylobacterium strains promoted the dominance of the toxic Microcystis aeruginosa PCC7806 when co‐culturing with the non‐toxic PCC7806 mcyB − mutant. Taken together, our data suggested that the α‐proteobacteria Phenylobacterium may play a vital role in the maintenance of toxic Microcystis dominance in Lake Taihu.

High expression of NEK2 promotes lung cancer progression and drug resistance and is regulated by mutant EGFR - Chuanhui Chen; Shanshan Peng; Penghui Li; Lin Ma; Xin Gan (Molecular and Cellular Biochemistry, 2020)

Mitigating Climate Change for Sugarcane Improvement: Role of Silicon in Alleviating Abiotic Stresses - Krishan K. Verma; Pratiksha Singh; Xiu-Peng Song; Mukesh Kumar Malviya; Rajesh Kumar Singh; Gan-Lin Chen; Sushil Solomon; Yang-Rui Li (Sugar Tech, 2020)

Rule-Based Object-Oriented Water Resource System Simulation Model for Water Allocation - Pengfei Lin; Jinjun You; Hong Gan; Ling Jia (Water Resources Management, 2020)
Simulation is a basic method to analyze water resources system and provide information for decision-making. In this study, a framework is presented that describes the basic elements in a water resource system and a modelling technique integrating conceptual simulation and rule control. To formulate the process of the water cycle and water exploitation with a mathematical model, the water system is described based on adjustable relevant rules and respective parameters with experiences and pragmatic demands in the framework. The rule set describes the principles required to design conceptual networks and control the concrete processes of movement and conversion of different water flows. Combined with object-oriented programming, different calculation functional modules are classified based on the characteristics of water source layers, and the processes that occur in the networks are realised in the computation. The influence of the South-to-North Water Diversion project on the Haihe River basin is analysed by the rule-based object-oriented water resource allocation simulation model. According to the simulation results, groundwater extraction will be reduced by 6,181 million m 3 . The relationship between water source replacement and water layer exchange in the Haihe River basin is analysed, and the feasibility of the model is verified. Based on the rule-based model, the user requirements can be taken into account conveniently, and the rules are flexible to adjust with experiences and real conditions. This model can be used to simulate complex water resource systems.

Three new phenylacetamide glycosides from Dracocephalum tanguticum Maxim and their anti-hyperglycemic activity - En-Guang Ma; Hai-Yan Wu; Li-Jiao Hu; Min Wei; Lin-Yun Mou; Gan-Peng Li (Natural Product Research, 2020)

Hypertrophic olivary degeneration: a single case report - Wei Jiang; Xiao-Zhong Jing; Lin Gan; Ming Dong; Peng Yu (Acta Neurologica Belgica, 2020)

Two new xanthone glycosides from Swertia punicea Hemsl. and their anti-inflammatory activity - Lin-Yun Mou; Hai-Yan Wu; En-Guang Ma; Ming-Feng Wang; Yan-Qing Duan; Sheng Lei; Gan-Peng Li (Natural Product Research, 2020)

First report of Fusarium oxysporum f. sp. canariensis causing Fusarium wilt on Canary Island date palm (Phoenix canariensis Hort. Ex Chabaud) in China - Cheng Zhong Lan; Yu Li Dai; Lin Gan; Jin Ai Yao; Xiu Juan Yang (Journal of Plant Pathology, 2020)

Effects of Elevated Ozone Concentrations on Root Characteristics and Soil Properties of Elaeocarpus sylvestris and Michelia chapensis - Lan Pan; Wan-qi Lin; Ming Yu; Gan-wen Lie; Li Xue; Hong-yue Chen (Bulletin of Environmental Contamination and Toxicology, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

A chronosequence study of purple paddy soils with respect to improving ammonium and potassium fertilization management - Guang-Zhong Han; Lai-Ming Huang; Gan-Lin Zhang; Fan Yang (Journal of Soils and Sediments, 2020)

Oil palm plantation mapping from high-resolution remote sensing images using deep learning - Runmin Dong; Weijia Li; Haohuan Fu; Lin Gan; Le Yu; Juepeng Zheng; Maocai Xia (International Journal of Remote Sensing, 2020)

Correction to: Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Characterization of the complete chloroplast genome of Cephalotaxus sinensis (Cupressales: Taxaceae), an endangered Tertiary relict tree endemic to China - Ren-Yan Duan; Li-Min Yang; Gan-Lin Wu (Conservation Genetics Resources, 2019)

Atmospheric deposition and air–soil exchange of polybrominated diphenyl ethers (PBDEs) in a background site in Central China - Lingxi Zhan; Tian Lin; Hairong Cheng; Zuwu Wang; Zhineng Cheng; Deng Zhou; Zhengxin Qin; Gan Zhang (Environmental Science and Pollution Research, 2019)

Multi‐omic analyses of exogenous nutrient bag decomposition by the black morel Morchella importuna reveal sustained carbon acquisition and transferring - Hao Tan; Annegret Kohler; Renyun Miao; Tianhai Liu; Qiang Zhang; Bo Zhang; Lin Jiang; Yong Wang; Liyuan Xie; Jie Tang; Xiaolin Li; Lixu Liu; et al. (Environmental Microbiology, 2019)
Summary The black morel ( Morchella importuna Kuo, O'Donnell and Volk) was once an uncultivable wild mushroom, until the development of exogenous nutrient bag (ENB), making its agricultural production quite feasible and stable. To date, how the nutritional acquisition of the morel mycelium is fulfilled to trigger its fruiting remains unknown. To investigate the mechanisms involved in ENB decomposition, the genome of a cultivable morel strain ( M . importuna SCYDJ1‐A1) was sequenced and the genes coding for the decay apparatus were identified. Expression of the encoded carbohydrate‐active enzymes (CAZymes) was then analyzed by metatranscriptomics and metaproteomics in combination with biochemical assays. The results show that a diverse set of hydrolytic and redox CAZymes secreted by the morel mycelium is the main force driving the substrate decomposition. Plant polysaccharides such as starch and cellulose present in ENB substrate (wheat grains plus rice husks) were rapidly degraded, whereas triglycerides were accumulated initially and consumed later. ENB decomposition led to a rapid increase in the organic carbon content in the surface soil of the mushroom bed, which was thereafter consumed during morel fruiting. In contrast to the high carbon consumption, no significant acquisition of nitrogen was observed. Our findings contribute to an increasingly detailed portrait of molecular features triggering morel fruiting.

A Damped Dynamic Finite Difference Approach for Modeling Static Stress–Strain Fields - Rongrong Lin; Xinding Fang; Yuandi Gan; Yingcai Zheng (Pure and Applied Geophysics, 2019)

Comprehensive transcriptomics and proteomics analyses of rice stripe virus-resistant transgenic rice - Yang Xu; Lvjie Bi; Zipeng Yu; Chao Lin; Liming Gan; Lifei Zhu; Haiyang Li; Yunzhi Song; Changxiang Zhu (Journal of Biosciences, 2019)

Spatial Distribution of Organophosphorus and Brominated Flame Retardants in Surface Water, Sediment, Groundwater, and Wild Fish in Chengdu, China - Lin Hou; Jingyan Jiang; Zhiwei Gan; YuanYuan Dai; Ping Yang; Yan Yan; Sanglan Ding; Shijun Su; Xiaoming Bao (Archives of Environmental Contamination and Toxicology, 2019)

Hispanic Spinocerebellar Ataxia Type 35 (SCA35) with a Novel Frameshift Mutation - Chih-Chun Lin; Shi-Rui Gan; Deepak Gupta; Armin Alaedini; Peter H Green; Sheng-Han Kuo (The Cerebellum, 2019)

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Effects of Long-Term Application of Vinasse on Physicochemical Properties, Heavy Metals Content and Microbial Diversity in Sugarcane Field Soil - Juan Yin; Chao-Bing Deng; Xiao-Fei Wang; Gan-lin Chen; Viktor Gábor Mihucz; Gui-Ping Xu; Qu-Cheng Deng (Sugar Tech, 2019)

Thermo-elastoplastic Model for Soft Rock Considering Effects of Structure and Overconsolidation - Yong-lin Xiong; Qi-lai Yang; Sheng Zhang; Guan-lin Ye; Gan-bin Liu; Rong-yue Zheng; Feng Zhang (Rock Mechanics and Rock Engineering, 2018)

DNA barcoding of traded shark fins, meat and mobulid gill plates in Singapore uncovers numerous threatened species - Benjamin J. Wainwright; Yin Cheong Aden Ip; Mei Lin Neo; Jia Jin Marc Chang; Chester Zhikai Gan; Naomi Clark-Shen; Danwei Huang; Madhu Rao (Conservation Genetics, 2018)

The ecological risks of hydrogen peroxide as a cyanocide: its effect on the community structure of bacterioplankton - Lizhou Lin; Kun Shan; Qian Xiong; Qichao Zhou; Lin Li; Nanqin Gan; Lirong Song (Journal of Oceanology and Limnology, 2018)

Sensitivity of Cochliobolus heterostrophus to three demethylation inhibitor fungicides, propiconazole, diniconazole and prochloraz, and their efficacy against southern corn leaf blight in Fujian Province, China - Yuli Dai; Lin Gan; Hongchun Ruan; Niuniu Shi; Yixin Du; Lei Liao; Zhixia Wei; Zhenyong Teng; Furu Chen; Xiujuan Yang (European Journal of Plant Pathology, 2018)

Bioaccumulation and Cycling of Polycyclic Aromatic Hydrocarbons (PAHs) in Typical Mangrove Wetlands of Hainan Island, South China - Yao-Wen Qiu; Han-Lin Qiu; Jun Li; Gan Zhang (Archives of Environmental Contamination and Toxicology, 2018)

New podolactones from the seeds of Podocarpus nagi and their anti-inflammatory effect - Zhe-Ling Feng; Tian Zhang; Jing-Xin Liu; Xiu-Ping Chen; Li-She Gan; Yang Ye; Li-Gen Lin (Journal of Natural Medicines, 2018)

Identification of novel miRNAs and their target genes in Eucalyptus grandis - Zheng Lin; Qingfen Li; Qi Yin; Jinyan Wang; Baolong Zhang; Siming Gan; Ai-Min Wu (Tree Genetics & Genomes, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Reach and messages of the world's largest ivory burn - Alexander Braczkowski; Matthew H. Holden; Christopher O'Bryan; Chi‐Yeung Choi; Xiaojing Gan; Nicholas Beesley; Yufang Gao; James Allan; Peter Tyrrell; Daniel Stiles; Peadar Brehony; Revocatus Meney; et al. (Conservation Biology, 2018)
Recent increases in ivory poaching have depressed African elephant populations. Successful enforcement has led to ivory stockpiling. Stockpile destruction is becoming increasingly popular, and most destruction has occurred in the last 5 years. Ivory destruction is intended to send a strong message against ivory consumption, both in promoting a taboo on ivory use and catalyzing policy change. However, there has been no effort to establish the distribution and extent of media reporting on ivory destruction events globally. We analyzed media coverage of the largest ivory destruction event in history (Kenya, 30 April 2016) across 11 nation states connected to ivory trade. We used an online‐media crawling tool to search online media outlets and subjected 5 of the largest print newspapers (by circulation) in 5 nations of interest to content analysis. Most online news on the ivory burn came from the United States (81% of 1944 articles), whereas most of the print news articles came from Kenya (61% of 157 articles). Eighty‐six to 97% of all online articles reported the burn as a positive conservation action, whereas 4–50% discussed ivory burning as having a negative impact on elephant conservation. Most articles discussed law enforcement and trade bans as effective for elephant conservation. There was more relative search interest globally in the 2016 Kenyan ivory burn than any other burn in 5 years. Ours is the first attempt to track the reach of media coverage relative to an ivory burn and provides a case study in tracking the effects of a conservation‐marketing event.

Effects of different initial pH and irradiance levels on cyanobacterial colonies from Lake Taihu, China - Fei Fang; Yan Gao; Lin Gan; Xiaoyun He; Liuyan Yang (Journal of Applied Phycology, 2018)

Lhx9 Is Required for the Development of Retinal Nitric Oxide-Synthesizing Amacrine Cell Subtype - Revathi Balasubramanian; Andrew Bui; Xuhui Dong; Lin Gan (Molecular Neurobiology, 2018)

The complete mitochondrial genome sequence of Changbai Mountains wild boar (Cetartiodactyla: Suidae) - Zhen-Dong Tan; Lin-Yuan Shen; Xiao Cheng; Mai-Lin Gan; Shun-Hua Zhang; Li Zhu (Conservation Genetics Resources, 2018)

ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Diversity of microbiota associated with symptomatic and non-symptomatic bacterial wilt-diseased banana plants determined using 16S rRNA metagenome sequencing - Nurul Shamsinah Mohd Suhaimi; Share-Yuan Goh; Noni Ajam; Rofina Yasmin Othman; Kok-Gan Chan; Kwai Lin Thong (World Journal of Microbiology and Biotechnology, 2017)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

Soil organic phosphorus transformation during ecosystem development: A review - Lai-Ming Huang; Xiao-Xu Jia; Gan-Lin Zhang; Min-An Shao (Plant and Soil, 2017)

Barhl2 Determines the Early Patterning of the Diencephalon by Regulating Shh - Qian Ding; Revathi Balasubramanian; Dongwang Zheng; Guoqing Liang; Lin Gan (Molecular Neurobiology, 2017)

Two new phenylpropanoids from Swertia atroviolacea and their anti-5 α -reductase activity - Hai-Yan Wu; Xue-Qing Kan; Yu Sheng; Lin-Yun Mou; Qing-Song Yang; Qiu-Feng Hu; Gan-Peng Li (Natural Product Research, 2017)

Effect of Nitrite on the Formation of Trichloronitromethane (TCNM) During Chlorination of Polyhydroxy-Phenols and Sugars - Guojuan Gan; Lin Qiu; Huan Wu; Huachang Hong; Asit Mazumder; Xiangliang Pan; Yan Liang (Water, Air, & Soil Pollution, 2017)

Isolation and purification of antialgal compounds from the red alga Gracilaria lemaneiformis for activity against common harmful red tide microalgae - Ying-ying Sun; Kun Meng; Zhen-xia Su; Gan-lin Guo; Yin-fang Pu; Chang-hai Wang (Environmental Science and Pollution Research, 2017)

Design, synthesis, and antimicrobial activities of new tanshinone IIA esters - Lin-Wei Zeng; Chang-Xin Zhou; Jia-Dong Liu; Chang-Hong Liu; Jian-Xia Mo; A-Fang Hou; Wei Yao; Zhen-Zhen Wang; Li-She Gan (Natural Product Research, 2016)

The complete chloroplast genome sequence of Pinus dabeshanensis - Ren-Yan Duan; Li-Min Yang; Tong Lv; Gan-Lin Wu; Min-Yi Huang (Conservation Genetics Resources, 2016)

Characterization of the spatial variability of soil available zinc at various sampling densities using grouped soil type information - Xiao-Dong Song; Gan-Lin Zhang; Feng Liu; De-Cheng Li; Yu-Guo Zhao (Environmental Monitoring and Assessment, 2016)

Controlling effects of surface crusts on water infiltration in an arid desert area of Northwest China - Jin-Ling Yang; Gan-Lin Zhang; Fei Yang; Ren-Min Yang; Chen Yi; De-Cheng Li; Yu-Guo Zhao; Feng Liu (Journal of Soils and Sediments, 2016)

Plant food sources and stone tools’ function at the site of Shunshanji based on starch grain analysis - YuZhang Yang; WeiYa Li; Ling Yao; ZhiJie Cheng; WuHong Luo; JuZhong Zhang; LiuGen Lin; HuiYuan Gan; Long Yan (Science China Earth Sciences, 2016)

Wax crystal-sparse leaf 3 encoding a β-ketoacyl-CoA reductase is involved in cuticular wax biosynthesis in rice - Lu Gan; Xiaole Wang; Zhijun Cheng; Linglong Liu; Jiulin Wang; Zhe Zhang; Yulong Ren; Cailin Lei; Zhichao Zhao; Shanshan Zhu; Qibing Lin; Fuqing Wu; et al. (Plant Cell Reports, 2016)

From folding to transpressional faulting: the Cenozoic Fusha structural belt in front of the Western Kunlun Orogen, northwestern Tibetan Plateau - Cong Wang; Xiao-Gan Cheng; Han-Lin Chen; Kang Li; Xiao-Gen Fan; Chun-Yang Wang (International Journal of Earth Sciences, 2016)

Correlation between the germline methylation status in ERβ promoter and the risk in prostate cancer: a prospective study - Lihui Wang; Pan Zhang; Xiannan Meng; Xiang Chen; Zou Xiang; Xiaoqian Lin; Ye Liu; Weidong Gan; Xiaodong Han; Dongmei Li (Familial Cancer, 2016)

Improved random noise attenuation using f−x empirical mode decomposition and local similarity - Shu-Wei Gan; Shou-Dong Wang; Yang-Kang Chen; Jiang-Long Chen; Wei Zhong; Cheng-Lin Zhang (Applied Geophysics, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Isolation, purification, and identification of antialgal substances in green alga Ulva prolifera for antialgal activity against the common harmful red tide microalgae - Ying-ying Sun; Hui Wang; Gan-lin Guo; Yin-fang Pu; Bin-lun Yan; Chang-hai Wang (Environmental Science and Pollution Research, 2016)

Biosorption of Hg(II) and Cu(II) by biomass of dried Sargassum fusiforme in aquatic solution - Shengmou Huang; Gan Lin (Journal of Environmental Health Science and Engineering, 2015)

Design, synthesis and antiproliferative evaluation of some B-homo steroidal lactams - Jianguo Cui; Qifu Lin; Yanmin Huang; Chunfang Gan; Qiucui Yao; Yingliang Wei; Qi Xiao; Erbin Kong (Medicinal Chemistry Research, 2015)

Green alga Ulva pertusa—a new source of bioactive compounds with antialgal activity - Sun Ying-ying; Wang Hui; Guo Gan-lin; Pu Yin-fang; Yan Bin-lun; Wang Chang-hai (Environmental Science and Pollution Research, 2015)

Association Between a Variant in ADAMTS5 and the Susceptibility to Hepatocellular Carcinoma in a Chinese Han Population - Chongyi Li; Yanli Xiong; Zhaoyang Zhong; Shiheng Zhang; Yu Peng; Lin’ang Wang; Nan Dai; Mengxia Li; Tao Ren; Lixia Gan; Dong Wang (Cell Biochemistry and Biophysics, 2015)

Baseflow characteristics in alpine rivers — a multi-catchment analysis in Northwest China - Rong Gan; Lin Sun; Yi Luo (Journal of Mountain Science, 2015)

Production and Characteristics of High Quality Vinegar from Sugarcane Juice - Gan-Lin Chen; Feng-Jin Zheng; Jian Sun; Zhi-Chun Li; Bo Lin; Yang-Rui Li (Sugar Tech, 2015)

Pedogenetic evolution of clay minerals and agricultural implications in three paddy soil chronosequences of south China derived from different parent materials - Guang-Zhong Han; Gan-Lin Zhang; De-Cheng Li; Jin-Ling Yang (Journal of Soils and Sediments, 2015)

Bacillus vanillea sp. nov., Isolated from the Cured Vanilla Bean - Yong-gan Chen; Feng-lin Gu; Ji-hua Li; Fei Xu; Shu-zhen He; Yi-ming Fang (Current Microbiology, 2015)

Enrichment of cardiac differentiation by a large starting number of embryonic stem cells in embryoid bodies is mediated by the Wnt11-JNK pathway - Ming Chen; Cheng Qian; Lin-Lin Bi; Fang Zhao; Guang-Yu Zhang; Zhi-Quan Wang; Xue-Dong Gan; Yang-Gan Wang (Biotechnology Letters, 2015)

Feasibility of treating aged polycyclic aromatic hydrocarbons (PAHs)-contaminated soils using ethyl lactate-based Fenton treatment via parametric and kinetic studies - Chiew Lin Yap; Suyin Gan; Hoon Kiat Ng (Environmental Science and Pollution Research, 2015)

Double homeobox gene, Duxbl, promotes myoblast proliferation and abolishes myoblast differentiation by blocking MyoD transactivation - Shey-Lin Wu; Guo-Zili Li; Chin-Yi Chou; Ming-Shiun Tsai; Yi-Pei Chen; Chung-Jung Li; Gan-Guang Liou; Wen-Wei Chang; Shen-Liang Chen; Sue-Hong Wang (Cell and Tissue Research, 2014)

In vitro cytotoxicity, cell cycle arrest, and antioxidation studies of ruthenium(II) complex [Ru(dmb)2(AHPIP)](ClO4)2 - De-Gang Xing; Yan Zhang; Gan-Jian Lin; Yang-Yin Xie; Shu-Yong Deng; Hong-Liang Huang; Guang-Bin Jiang; Yun-Jun Liu (Medicinal Chemistry Research, 2014)

Infected peripheral blood mononuclear cells transmit latent varicella zoster virus infection to the guinea pig enteric nervous system - Lin Gan; Mingli Wang; Jason J. Chen; Michael D. Gershon; Anne A. Gershon (Journal of NeuroVirology, 2014)

DO, pH, and Eh microprofiles in cyanobacterial granules from Lake Taihu under different environmental conditions - Fei Fang; Liuyang Yang; Lin Gan; Liyun Guo; Zhixin Hu; Sijia Yuan; Qiankun Chen; Lijuan Jiang (Journal of Applied Phycology, 2014)

Mapping Soil Particle Size Fractions Using Compositional Kriging, Cokriging and Additive Log-ratio Cokriging in Two Case Studies - Xiao-Lin Sun; Yun-Jin Wu; Hui-Li Wang; Yu-Guo Zhao; Gan-Lin Zhang (Mathematical Geosciences, 2014)

Bacterial community compositions of tomato (Lycopersicum esculentum Mill.) seeds and plant growth promoting activity of ACC deaminase producing Bacillus subtilis (HYT-12-1) on tomato seedlings - Mingshuang Xu; Jiping Sheng; Lin Chen; Yejun Men; Lin Gan; Shuntang Guo; Lin Shen (World Journal of Microbiology and Biotechnology, 2014)

Preparation and Characteristics of Sugarcane Low Alcoholic Drink by Submerged Alcoholic Fermentation - Gan-Lin Chen; Feng-Jin Zheng; Bo Lin; Tian-Shun Wang; Yang-Rui Li (Sugar Tech, 2013)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Cytotoxicity, apoptosis, cell cycle arrest, reactive oxygen species, mitochondrial membrane potential, and Western blotting analysis of ruthenium(II) complexes - Gan-Jian Lin; Guang-Bin Jiang; Yang-Yin Xie; Hong-Liang Huang; Zhen-Hua Liang; Yun-Jun Liu (JBIC Journal of Biological Inorganic Chemistry, 2013)

Benzothiazole Schiff-bases as potential imaging agents for β-amyloid plaques in Alzheimer’s disease - Changsheng Gan; Lin Zhou; Zhenzhen Zhao; Haoshu Wang (Medicinal Chemistry Research, 2013)

Time-dependent regulation of neuregulin-1β/ErbB/ERK pathways in cardiac differentiation of mouse embryonic stem cells - Ming Chen; Lin-Lin Bi; Zhi-Quan Wang; Fang Zhao; Xue-Dong Gan; Yang-Gan Wang (Molecular and Cellular Biochemistry, 2013)

Anatomical adaptations of the xerophilous medicinal plant, Capparis spinosa, to drought conditions - Lu Gan; Chunyu Zhang; Yongtai Yin; Zhiwei Lin; Yongwei Huang; Jun Xiang; Chunhua Fu; Maoteng Li (Horticulture, Environment, and Biotechnology, 2013)

Association between HFE polymorphisms and susceptibility to Alzheimer’s disease: a meta-analysis of 22 studies including 4,365 cases and 8,652 controls - Min Lin; Lin Zhao; Jin Fan; Xue-Gan Lian; Jian-xin Ye; Lei Wu; Hang Lin (Molecular Biology Reports, 2012)

Associations between common variants in GC and DHCR7/NADSYN1 and vitamin D concentration in Chinese Hans - Ling Lu; Hongguang Sheng; Huaixing Li; Wei Gan; Chen Liu; Jingwen Zhu; Ruth J. F. Loos; Xu Lin (Human Genetics, 2012)

The role of microcystins in maintaining colonies of bloom‐forming Microcystis spp. - Nanqin Gan; Yan Xiao; Lin Zhu; Zhongxing Wu; Jin Liu; Chenlin Hu; Lirong Song (Environmental Microbiology, 2012)
Summary Microcystis is a cosmopolitan genus of cyanobacteria and occurs in many different forms. Large surface blooms of the cyanobacterium are well known in eutrophic lakes throughout the globe. We evaluated the role of microcystins (MCs) in promoting and maintaining bloom‐forming cell aggregates at environmentally relevant MC concentrations (0.25–10 µg l −1 ). MCs significantly enhanced Microcystis colony sizes. Colonial diameters in microcystin‐RR (MC‐RR)‐treated cultures (at 1 µg l −1 ) were significantly larger than control colonies, by factors of 1.5, 2.6 and 2.7 in Microcystis wesenbergii DC‐M1, M. ichthyoblabe TH‐M1 and Microcystis sp. FACHB1027 respectively. Depletion of extracellular MC concentrations caused Microcystis colony size to decrease, suggesting that released MCs are intimately involved in the maintenance of Microcystis colonial size. MC‐RR exposure did not influence Microcystis growth rate, but did significantly increase the production of extracellular polysaccharides (EPS). In addition, MC‐RR exposure appeared to trigger upregulation of certain parts of four polysaccharide biosynthesis‐related genes: capD , csaB , tagH and epsL . These results strongly indicate that induction of polysaccharides by MC‐RR was the major mechanism through which MCs enhanced colony formation in Microcystis spp. Cellular release of MCs, therefore, may play a key role in the persistence of algal colonies and the dominance of Microcystis.

Sorption and persistence of wastewater-borne psychoactive and antilipidemic drugs in soils - Kunde Lin; Svetlana Bondarenko; Jay Gan (Journal of Soils and Sediments, 2011)

Water infiltration in urban soils and its effects on the quantity and quality of runoff - Jin-Ling Yang; Gan-Lin Zhang (Journal of Soils and Sediments, 2011)

Effect of ammonia and nitrite on vigour, survival rate, moulting rate of the blue swimming crab Portunus pelagicus zoea - Yong Yang Liao; Hong Hu Wang; Zhi Gan Lin (Aquaculture International, 2011)

Effects of farnesoid X receptor on the expression of the fatty acid synthetase and hepatic lipase - Li-Li Shen; Hong Liu; Jiahe peng; Lin Gan; Li Lu; Qian Zhang; Liangpeng Li; Fengtian He; Yu Jiang (Molecular Biology Reports, 2011)

Genetic analysis of the VP1 region of enterovirus 71 reveals the emergence of genotype A in central China in 2008 - Haiyang Yu; Wei Chen; Hongwei Chang; Renshu Tang; Jun Zhao; Lin Gan; Boyu Liu; Jason Chen; Mingli Wang (Virus Genes, 2010)

Morphologic observation and classification criteria of atretic follicles in guinea pigs - Wei Wang; Hong-lin Liu; Wei Tian; Fen-fen Zhang; Yan Gong; Jin-wei Chen; Da-gan Mao; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2010)

Sorption of the herbicide terbuthylazine in two New Zealand forest soils amended with biosolids and biochars - Hailong Wang; Kunde Lin; Zhenan Hou; Brian Richardson; Jay Gan (Journal of Soils and Sediments, 2010)

Leaf callus induction and suspension culture establishment in lychee (Litchi chinensis Sonn.) cv. Huaizhi - Xin-Ye Ma; Gan-Jun Yi; Xue-Lin Huang; Ji-Wu Zeng (Acta Physiologiae Plantarum, 2009)

Land use impact on nitrogen discharge by stream: a case study in subtropical hilly region of China - Jin-Ling Yang; Gan-Lin Zhang; Yu-Guo Zhao (Nutrient Cycling in Agroecosystems, 2007)

Biological and ecological features of saline lakes in northern Tibet, China - Zhao Wen; Zheng Mian-ping; Xu Xian-zhong; Liu Xi-Fang; Guo Gan-lin; He Zhi-hui (Hydrobiologia, 2005)

On seismic inversion - F. Baman; Hongrui xia; Yun Lin; Lideng Gan (Applied Geophysics, 2004)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Exploring suitability for tropical crop cultivation in Hainan Island by SOTAL methodology - Zhang Xue-lei; S. Mantel; Zhang Gan-lin; V. W. P. van Engelen (Journal of Geographical Sciences, 2001)

Mercury pollution from small gold mines in China - Yuhuan Lin; Mingxin Guo; Weiming Gan (Water, Air, & Soil Pollution, 1997)

Mercury Pollution from Small Gold Mines in China - Yuhuan Lin; Mingxin Guo; Weiming Gan (Water, Air, & Soil Pollution, 1997)